All-solid-state secondary battery, composition, sheet and manufacturing method
By using a composition containing inorganic solid electrolytes and specific official groups in the full solid secondary battery, the problem of decreased resistance and cycle characteristics of the resistance of solid particles during the charging and discharge process is solved.
Patent Information
- Application Number
- CN202080066902.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-27
- Filing Date
- 2020-09-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-09-25
AI Technical Summary
During the charging and discharging process of an all-solid secondary battery, the contact state between solid particles decreases, resulting in an increase in resistance and a decrease in cycle characteristics.
A composition containing inorganic solid electrolytes contains conductive inorganic solid electrolytes (SA) of the 1st or 2nd metal ions with a periodic table of the 1st or 2nd clan to inhibit the gap caused by the power supply.
By reducing the friction resistance between solid particles, maintaining the density of the active material layer during the charge and discharge process, reducing the resistance and improving the circulation characteristics.
Smart Images

Figure CN114531927B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composition containing an inorganic solid electrolyte, a sheet for an all-solid-state secondary battery, an electrode sheet for an all-solid-state secondary battery, an all-solid-state secondary battery, and a method for manufacturing the sheet for an all-solid-state secondary battery and the all-solid-state secondary battery. Background Art
[0002] In all-solid-state secondary batteries, all negative electrodes, electrolytes, and positive electrodes are made of solids, which can greatly improve the safety or reliability of batteries using organic electrolytes as a subject. And it can also extend the life. In addition, all-solid-state secondary batteries can be set as a structure in which electrodes and electrolytes are directly arranged and configured in series. Therefore, compared with secondary batteries using organic electrolytes, it can become high energy density, and it is expected to be applied to electric vehicles or large batteries.
[0003] In such all-solid-state secondary batteries, as materials forming constituent layers (solid electrolyte layer, negative electrode active material layer, positive electrode active material layer, etc.), solid particle materials such as inorganic solid electrolytes, active materials, and conductive additives are used. Therefore, the materials forming such constituent layers (constituent layer forming materials) usually use, in addition to solid particle materials, materials such as adhesives for bonding solid particle materials and dispersants dispersed in a dispersion medium.
[0004] For example, Patent Document 1 describes a positive electrode material, which contains a positive electrode active material, an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a conductive aid, and a dispersant comprising a compound having a specific functional group. Patent Document 2 describes a solid electrolyte composition, which contains (A) an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a fluorine-containing compound satisfying specific conditions at a specific content of (B), and (C) a dispersion medium. Patent Document 3 describes a solid electrolyte composition, which contains an inorganic solid electrolyte (A) having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and a compound (B) represented by a specific formula as a polymer dispersant.
[0005] In addition, it is proposed to use a solid electrolyte material obtained by pre-surface treating the solid electrolyte, rather than using a constituent layer forming material together with an inorganic solid electrolyte, etc. For example, Patent Document 4 describes a solution containing a lithium battery coated solid electrolyte and a binder in which the surface of a sulfide-based solid electrolyte containing at least lithium and phosphorus is coated with a fluorine-containing silane compound or a fluorine-containing acrylic resin.
[0006] Previous technical literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2016 / 194759
[0009] Patent Document 2: International Publication No. 2018 / 016544
[0010] Patent Document 3: International Publication No. 2016 / 136089
[0011] Patent Document 4: Japanese Patent Application Publication No. 2010-033732 Summary of the invention
[0012] Technical issues to be solved by the invention
[0013] In the constituent layer formed by solid particle materials (also referred to as solid particles), generally, the interface contact state between solid particles (for example, between inorganic solid electrolytes, between inorganic solid electrolytes and active materials, between active materials) is insufficient. In addition, when the constituent layer of the all-solid-state secondary battery, especially the active material layer, is repeatedly expanded and contracted by charge and discharge (with the shrinkage and expansion of the active material caused by the release and absorption of the ions of the metal belonging to the first or second group of the periodic table), the contact state of the solid particles is gradually reduced. In particular, the (negative electrode) active material that can form an alloy with lithium shows high ionic conductivity, which is concerned in terms of helping to improve basic battery performance, but on the other hand, due to the large expansion and contraction caused by charge and discharge, the contact state of the solid particles is significantly reduced. It is believed that the reduction in the contact state of this solid particle is due to the gradual generation of gaps between the solid particles in the constituent layer, which not only increases the resistance of the all-solid-state secondary battery, but also reduces the cycle characteristics.
[0014] The subject of the present invention is to provide a composition containing an inorganic solid electrolyte, which can be used as a constituent layer forming material of an all-solid-state secondary battery to achieve a constituent layer capable of suppressing the generation of voids due to the charge and discharge of the all-solid-state secondary battery. In addition, the subject of the present invention is to provide a sheet for an all-solid-state secondary battery, an electrode sheet for an all-solid-state secondary battery, and an all-solid-state secondary battery, and a method for manufacturing the sheet for an all-solid-state secondary battery and the all-solid-state secondary battery using the composition containing an inorganic solid electrolyte.
[0015] Means for solving technical problems
[0016] The inventors of the present invention have repeatedly conducted various studies and found that the composition containing an inorganic solid electrolyte, which has a specific molecular structure and a compound (SA) with a specific functional group, is used as a constituent layer forming material for an all-solid-state secondary battery, thereby being able to achieve a constituent layer that is difficult to produce gaps during the expansion and contraction of the constituent layer caused by charging and discharging due to the reduction of frictional resistance between solid particles. In addition, it was found that by using a constituent layer formed by the composition containing an inorganic solid electrolyte as a sheet for an all-solid-state secondary battery or a constituent layer of an all-solid-state secondary battery, the resistance of the all-solid-state secondary battery can be reduced and the cycle characteristics can be improved. The present invention has been further repeatedly studied based on these insights, thereby completing the present invention.
[0017] That is, the above-mentioned problems are solved by the following means.
[0018] <1> A composition containing an inorganic solid electrolyte, comprising an inorganic solid electrolyte having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and at least one compound (SA) selected from the following (A) to (C).
[0019] (A): A compound represented by the following formula (1)
[0020] Formula (1) RAX
[0021] In formula (1), R represents an aliphatic hydrocarbon group having 6 or more carbon atoms and not having fluorine atoms, or represents a group comprising a fluorinated hydrocarbon group and a hydrocarbon group having no fluorine atoms, wherein the aliphatic hydrocarbon group does not contain a steroid ring structure. A represents a divalent linking group that does not contain an aromatic ring structure. X represents a functional group represented by the following functional group group (I).
[0022] (B): Perfluoropolyether, polychlorotrifluoroethylene or polytetrafluoroethylene having at least one functional group among the functional groups included in the following functional group group (I)
[0023] (C): an organopolysiloxane having at least one functional group among the functional groups included in the following functional group group (I)
[0024] <Functional group (I)>
[0025] Acidic group, group having basic nitrogen atom, amide group, urea group, urethane group, alkoxysilyl group, epoxy group, isocyanate group, hydroxyl group or (meth)acryloyloxy group
[0026] <2> The composition containing an inorganic solid electrolyte according to <1>, wherein
[0027] The ratio of the content of the inorganic solid electrolyte [SE] to the total content of the compound (SA) [SA] in 100% by mass of the solid content of the composition containing the inorganic solid electrolyte: [SA] / [SE] is 0.0003 to 0.11.
[0028] <3> The inorganic solid electrolyte-containing composition according to <1> or <2>, further comprising a polymer binder.
[0029] <4> The composition containing an inorganic solid electrolyte according to <3>, wherein
[0030] The ratio of the content [BR] of the polymer binder to the total content [SA] of the compound (SA) in 100% by mass of the solid content of the composition containing the inorganic solid electrolyte: [BR] / [SA] is 0.2 to 5.
[0031] <5> The inorganic solid electrolyte-containing composition according to any one of <1> to <4>, comprising an active material.
[0032] <6> The composition containing an inorganic solid electrolyte according to <5>, wherein
[0033] The active material is an active material containing silicon element or tin element.
[0034] <7> The composition containing an inorganic solid electrolyte according to any one of <1> to <6>, wherein
[0035] Compound (SA) includes a compound represented by formula (1).
[0036] <8> The composition containing an inorganic solid electrolyte according to any one of <1> to <7>, wherein
[0037] The inorganic solid electrolyte is a sulfide-based inorganic solid electrolyte.
[0038] <9> The inorganic solid electrolyte-containing composition according to any one of <1> to <8>, further comprising a dispersion medium.
[0039] <10> The composition containing an inorganic solid electrolyte according to any one of <1> to <9>, wherein
[0040] The dispersion medium is selected from ketone compounds, aliphatic compounds and ester compounds.
[0041] <11> A sheet for an all-solid-state secondary battery, comprising a layer composed of the composition containing an inorganic solid electrolyte according to any one of <1> to <10> above.
[0042] <12> An electrode sheet for an all-solid-state secondary battery, comprising an active material layer formed of the composition containing an inorganic solid electrolyte according to any one of <5> to <6> above.
[0043] <13> An all-solid-state secondary battery comprising, in order, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein:
[0044] At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is a layer composed of the composition containing an inorganic solid electrolyte described in any one of <1> to <10>.
[0045] <14> A method for producing a sheet for an all-solid-state secondary battery, comprising forming a film of the composition containing an inorganic solid electrolyte according to any one of <1> to <10> above.
[0046] <15> A method for manufacturing an all-solid-state secondary battery, comprising manufacturing the all-solid-state secondary battery by the manufacturing method described in <14> above.
[0047] Effects of the Invention
[0048] The composition containing an inorganic solid electrolyte of the present invention can be used as a constituent layer forming material of an all-solid-state secondary battery to realize a constituent layer that can suppress the generation of voids by the charging and discharging of the all-solid-state secondary battery. In addition, the all-solid-state secondary battery sheet and the all-solid-state secondary battery electrode sheet of the present invention can be used as a constituent layer of an all-solid-state secondary battery to realize an all-solid-state secondary battery showing low resistance and excellent cycle characteristics. In addition, the all-solid-state secondary battery of the present invention shows low resistance and excellent cycle characteristics.
[0049] Furthermore, each method for producing the sheet for an all-solid-state secondary battery and the all-solid-state secondary battery of the present invention can produce the sheet for an all-solid-state secondary battery and the all-solid-state secondary battery that exhibit the above-mentioned excellent characteristics.
[0050] The above-mentioned features and other features and advantages of the present invention will become more apparent from the following description with appropriate reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a longitudinal sectional view schematically showing an all-solid-state secondary battery according to a preferred embodiment of the present invention.
[0052] Figure 2 It is a longitudinal sectional view schematically showing an all-solid-state secondary battery (button battery) produced in the example. DETAILED DESCRIPTION
[0053] In the present invention, the numerical range represented by "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0054] In the present invention, the term "compound" (for example, when the term "compound" is appended to the end) includes not only the compound itself but also its salts and ions, and includes derivatives in which a part is changed by introducing a substituent, etc., within the range that does not impair the effects of the present invention.
[0055] In the present invention, (meth)acrylic acid refers to one or both of acrylic acid and methacrylic acid. The same applies to (meth)acrylate.
[0056] In the present invention, regarding the substituent, linking group, etc. (hereinafter referred to as substituent, etc.) that is not clearly recorded as substituted or unsubstituted, it means that the group may also have a suitable substituent. Therefore, in the present invention, even if it is simply recorded as a YYY group, the YYY group further includes a mode with a substituent in addition to the mode without a substituent. This is also the same for compounds that are not clearly recorded as substituted or unsubstituted. As a preferred substituent, for example, the substituent Z described later can be cited.
[0057] In the present invention, when there are multiple substituents etc. represented by specific symbols or when multiple substituents etc. are specified simultaneously or selectively, it means that each substituent etc. may be the same or different from each other. Furthermore, even if there is no special description, when multiple substituents etc. are adjacent, it means that these may be linked or fused to each other to form a ring.
[0058] In the present invention, polymer refers to a polymer, but has the same meaning as a so-called high molecular compound. In addition, a polymer binder (also simply referred to as a binder) refers to a binder composed of a polymer, including a polymer itself and a binder containing a polymer.
[0059] [Composition containing inorganic solid electrolyte]
[0060] The inorganic solid electrolyte-containing composition of the present invention contains an inorganic solid electrolyte having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and at least one compound (SA) selected from (A) to (C) described later.
[0061] In the composition containing an inorganic solid electrolyte of the present invention, the state of containing the inorganic solid electrolyte and the compound (SA) is not particularly limited, and solid particles such as the inorganic solid electrolyte and the compound (SA) may exist (disperse) independently. That is, the compound (SA) may be adsorbed or attached to the surface of the solid particles, or may not be adsorbed or attached, but is preferably adsorbed or attached.
[0062] The composition containing an inorganic solid electrolyte of the present invention can form a constituent layer that is difficult to generate voids even if the all-solid-state secondary battery is repeatedly charged and discharged, and can suppress the generation of voids for the active material layer that expands and contracts by charging and discharging, especially the negative electrode active material layer that expands and contracts greatly, and can maintain the desired contact state between the solid particles. The all-solid-state secondary battery with such a constituent layer can achieve low resistance and improved cycle characteristics by using the composition containing an inorganic solid electrolyte of the present invention as a constituent layer forming material of the all-solid-state secondary battery.
[0063] The above-mentioned effects are achieved by using the compound (SA) described later in combination with the inorganic solid electrolyte in the composition containing the inorganic solid electrolyte of the present invention. The detailed reason is not clear, but it is considered as follows.
[0064] That is, in the constituent layer formed by the composition containing the inorganic solid electrolyte, the compound (SA) used in combination with solid particles such as the inorganic solid electrolyte (in addition, active materials and conductive aids that can coexist) is attached or adsorbed to the solid particles (especially the inorganic solid electrolyte) through the functional group, usually on its surface. The solid particles adsorbed by the compound (SA) etc. show high sliding ability (sliding property) (showing small surface friction resistance) relative to other solid particles located nearby (for example, inorganic solid electrolytes each other, inorganic solid electrolytes and active materials, active materials each other) due to the intervention of the compound (SA). As a result, it is believed that the desired contact state between the solid particles can be maintained even by the expansion and contraction of the constituent layer.
[0065] For example, the active material layer is specifically described, and the active material layer expanded by charging of the all-solid-state secondary battery shrinks to a dense state by discharging so that the solid particles move without generating gaps. The all-solid-state secondary battery is usually subject to pressurization restrictions, thereby promoting the shrinkage of the dense active material layer. As long as the above-mentioned compound (SA) is inserted between the solid particles, this shrinkage of the dense active material layer can be repeatedly achieved.
[0066] As described above, the constituent layer containing the above-mentioned compound (SA) can suppress the voids caused by the charge and discharge of the all-solid-state secondary battery, especially the generation of the voids during contraction, and as a result, even if the all-solid-state secondary battery is charged and discharged, the desired contact state between the solid particles can be maintained. Therefore, the all-solid-state secondary battery having a constituent layer formed by the composition containing an inorganic solid electrolyte of the present invention can take into account both low resistance and cycle characteristics at a high level.
[0067] Although described in detail later, the above-mentioned effects of the present invention are further improved by using a polymer binder in combination, particularly by using an inorganic solid electrolyte, the above-mentioned compound (SA), and a polymer binder in combination at a specific content ratio.
[0068] The composition containing an inorganic solid electrolyte of the present invention can be preferably used as a sheet material for an all-solid-state secondary battery (including an electrode sheet for an all-solid-state secondary battery) or a forming material (constituent layer forming material) of a solid electrolyte layer or an active material layer of an all-solid-state secondary battery. In particular, it can be preferably used as a forming material for a negative electrode sheet or a negative electrode active material layer for an all-solid-state secondary battery containing a negative electrode active material with large expansion and contraction caused by charge and discharge, and in this way, a high active material capacity is shown, but low resistance and high cycle characteristics can also be achieved.
[0069] The composition containing an inorganic solid electrolyte of the present invention is preferably a non-aqueous composition. In the present invention, the non-aqueous composition, in addition to including a mode that does not contain water, also includes a mode in which the water content (also referred to as water content) is preferably 500ppm or less. In the non-aqueous composition, the water content is more preferably 200ppm or less, further preferably 100ppm or less, and particularly preferably 50ppm or less. If the composition containing an inorganic solid electrolyte is a non-aqueous composition, the degradation of the inorganic solid electrolyte can be suppressed. The water content represents the amount of water contained in the composition containing an inorganic solid electrolyte (to the mass ratio of the composition containing an inorganic solid electrolyte), specifically, it is set to a value obtained by filtering with a 0.02μm membrane filter and measuring using Karl Fischer titration.
[0070] The inorganic solid electrolyte-containing composition of the present invention also includes an embodiment in which it contains an active material, a conductive auxiliary agent, etc. in addition to the inorganic solid electrolyte (a composition of this embodiment is referred to as an electrode composition).
[0071] Hereinafter, components contained in and components that may be contained in the inorganic solid electrolyte composition of the present invention will be described.
[0072] <Inorganic solid electrolyte>
[0073] The inorganic solid electrolyte-containing composition of the present invention contains an inorganic solid electrolyte.
[0074] In the present invention, an inorganic solid electrolyte refers to an inorganic solid electrolyte, and a solid electrolyte refers to a solid electrolyte that enables ions to move inside it. Considering that an organic substance that is not included as the main ion conductive material is not included, it is clearly distinguished from an organic solid electrolyte (a polymer electrolyte represented by polyethylene oxide (PEO), etc., an organic electrolyte salt represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), etc.). In addition, since the inorganic solid electrolyte is solid in a stable state, it is usually not dissociated or freed into cations and anions. At this point, it is clearly distinguished from an inorganic electrolyte salt (LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), LiCl, etc.) that is dissociated or freed into cations and anions in an electrolyte or a polymer. As long as the inorganic solid electrolyte has the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, it is not particularly limited and usually does not have electronic conductivity. When the all-solid-state secondary battery of the present invention is a lithium-ion battery, the inorganic solid electrolyte preferably has ion conductivity of lithium ions.
[0075] The above-mentioned inorganic solid electrolyte can be appropriately selected from solid electrolyte materials commonly used in all-solid-state secondary batteries. For example, as inorganic solid electrolytes, (i) sulfide-based inorganic solid electrolytes, (ii) oxide-based inorganic solid electrolytes, (iii) halide-based inorganic solid electrolytes, and (iv) hydride-based inorganic solid electrolytes can be cited. From the perspective of being able to form a better interface between the active material and the inorganic solid electrolyte, sulfide-based inorganic solid electrolytes are preferred.
[0076] (i) Sulfide-based inorganic solid electrolytes
[0077] The sulfide-based inorganic solid electrolyte preferably contains a sulfur atom and has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and is an electronically insulating compound. The sulfide-based inorganic solid electrolyte preferably contains at least Li, S, and P as elements and has lithium ion conductivity, but may contain elements other than Li, S, and P depending on the purpose or circumstances.
[0078] Examples of the sulfide-based inorganic solid electrolyte include lithium ion conductive inorganic solid electrolytes having a composition represented by the following formula (S1).
[0079] La1Mb1Pc1Sd1Ae1(S1)
[0080] In the formula, L represents an element selected from Li, Na and K, preferably Li. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al and Ge. A represents an element selected from I, Br, Cl and F. a1~e1 represent the composition ratio of each element, and a1:b1:c1:d1:e1 satisfies 1~12:0~5:1:2~12:0~10. a1 is preferably 1~9, and more preferably 1.5~7.5. b1 is preferably 0~3, and more preferably 0~1. d1 is preferably 2.5~10, and more preferably 3.0~8.5. e1 is preferably 0~5, and more preferably 0~3.
[0081] As described below, the composition ratio of each element can be controlled by adjusting the blending amount of the raw material compound when producing the sulfide-based inorganic solid electrolyte.
[0082] The sulfide-based inorganic solid electrolyte may be amorphous (glass), crystallized (glass ceramic), or only partially crystallized. For example, Li-PS-based glass containing Li, P, and S or Li-PS-based glass ceramic containing Li, P, and S may be used.
[0083] Sulfide-based inorganic solid electrolytes can be manufactured by reacting at least two or more raw materials, for example, lithium sulfide (Li2S), phosphorus sulfide (for example, phosphorus pentasulfide (P2S5)), elemental phosphorus, elemental sulfur, sodium sulfide, hydrogen sulfide, lithium halide (for example, LiI, LiBr, LiCl) and sulfides of the elements represented by the above M (for example, SiS2, SnS, GeS2).
[0084] The ratio of Li2S to P2S5 in the Li-PS glass and Li-PS glass ceramics is preferably 60:40 to 90:10, and more preferably 68:32 to 78:22, in terms of the molar ratio of Li2S:P2S5. By setting the ratio of Li2S to P2S5 to this range, the lithium ion conductivity can be improved. Specifically, the lithium ion conductivity can be preferably set to 1×10- 4 S / cm or more, more preferably 1×10- 3 S / cm or more. Although there is no specific upper limit, it is actually 1×10- 1 S / cm or less.
[0085] As specific examples of sulfide-based inorganic solid electrolytes, the combination of raw materials is shown below. For example, Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SiS2-LiCl, Li2S-P2S5-SnS, Li2S-P2S5-Al2 S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12 etc. Among them, the mixing ratio of each raw material is not limited. As a method for synthesizing a sulfide-based inorganic solid electrolyte material using such a raw material composition, for example, an amorphization method can be cited. As an amorphization method, for example, a mechanical polishing method, a solution method, and a melt quenching method can be cited. It is possible to perform treatment at room temperature, thereby simplifying the manufacturing process.
[0086] (ii) Oxide-based inorganic solid electrolytes
[0087] The oxide-based inorganic solid electrolyte is preferably a compound that contains oxygen atoms, has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.
[0088] The ion conductivity of the oxide-based inorganic solid electrolyte is preferably 1×10- 6 S / cm or more, more preferably 5×10- 6 S / cm or more, particularly preferably 1×10- 5 S / cm or more. Although there is no specific upper limit, it is actually 1×10- 1 S / cm or less.
[0089] As specific examples of compounds, for example, LixaLayaTiO3〔xa satisfies 0.3≤xa≤0.7, ya satisfies 0.3≤ya≤0.7.〕(LLT); LixbLaybZrzbMbbmbOnb (Mbb is one or more elements selected from Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In and Sn. xb satisfies 5≤xb≤10, yb satisfies 1≤yb≤4, zb satisfies 1≤zb≤4, mb satisfies 0≤mb≤2, and nb satisfies 5≤nb≤20.); LixcBycMcczcOnc (Mcc is one or more elements selected from C, S, Al, Si, Ga , Ge, In and Sn. xc satisfies 0<xc≤5, yc satisfies 0<yc≤1, zc satisfies 0<zc≤1, nc satisfies 0<nc≤6. ); Lixd(Al, Ga)yd(Ti, Ge)zdSiadPmdOnd(xd satisfies 1≤xd≤3, yd satisfies 0≤yd≤1, zd satisfies 0≤zd≤2, ad satisfies 0≤ad≤1, md satisfies 1≤md≤7, nd satisfies 3≤nd≤13.); Li (3 -2xe ) MeexeDeeO (xe represents a number greater than or equal to 0 and less than or equal to 0.1, Mee represents a divalent metal atom. Dee represents a halogen atom or a combination of two or more halogen atoms.); LixfSiyfOzf (xf satisfies 1≤xf≤5, yf satisfies 0<yf≤3, and zf satisfies 1≤zf≤10.); LixgSygOzg (xg satisfies 1≤xg≤3, yg satisfies 0<yg≤2, and zg satisfies 1≤zg≤10.); Li3BO3; Li3BO3-Li2SO4; Li2O-B2O3-P2O5; Li2O-SiO2; Li6BaLa2Ta2O 12 ;Li3PO (4 -3 / 2w ) Nw (w satisfies w<1); Li with LISICON (Lithium superionic conductor) type crystal structure 3.5 Zn 0.25 GeO4; La with perovskite crystal structure 0.55 Li 0.35 TiO3; LiTi2P3O with NASICON (Natrium super ionic conductor) type crystal structure 12 ;Li 1+ xh+yh(Al, Ga)xh(Ti, Ge)2-xhSiyhP3-yhO 12(xh satisfies 0≤xh≤1, yh satisfies 0≤yh≤1.); Li7La3Zr2O with garnet crystal structure 12 (LLZ) etc.
[0090] Furthermore, phosphorus compounds containing Li, P, and O are also preferred. Examples thereof include lithium phosphate (Li3PO4); LiPON in which a part of oxygen in lithium phosphate is substituted with nitrogen; and LiPOD 1 (D 1 Preferably, it is one or more elements selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt and Au. ) etc.
[0091] In addition, LiA can also be preferably used 1 ON(A 1 It is one or more elements selected from Si, B, Ge, Al, C and Ga. ) etc.
[0092] (iii) Halide-based inorganic solid electrolytes
[0093] The halide-based inorganic solid electrolyte is preferably a compound containing halogen atoms, having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electron insulating properties.
[0094] There are no particular restrictions on the halide-based inorganic solid electrolyte, and examples thereof include LiCl, LiBr, LiI, and compounds such as Li3YBr6 and Li3YCl6 described in ADVANCED MATERIALS, 2018, 30, 1803075. Among them, Li3YBr6 and Li3YCl6 are preferred.
[0095] (iv) Hydride-based inorganic solid electrolytes
[0096] The hydride-based inorganic solid electrolyte is preferably a compound that contains hydrogen atoms, has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.
[0097] The hydride-based inorganic solid electrolyte is not particularly limited, and examples thereof include LiBH4, Li4(BH4)3I, and 3LiBH4-LiCl.
[0098] The inorganic solid electrolyte is preferably in the form of particles. In this case, the particle size (volume average particle size) of the inorganic solid electrolyte is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.1 μm or more. The upper limit is preferably 100 μm or less, more preferably 50 μm or less.
[0099] The particle size of the inorganic solid electrolyte is determined by the following steps. In a 20 mL sample bottle, the inorganic solid electrolyte particles are diluted with water (heptane in the case of substances unstable to water) to prepare a 1% dispersion. The diluted dispersion sample is irradiated with 1 kHz ultrasound for 10 minutes and then used immediately in the test. Using the dispersion sample, a laser diffraction / scattering particle size distribution measuring device LA-920 (trade name, manufactured by HORIBA, Ltd.) is used and 50 data collections are performed at a temperature of 25°C using a quartz cell for measurement to obtain the volume average particle size. For other detailed conditions, refer to the Japanese Industrial Standard (JIS) Z 8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Five samples are prepared for each level and their average value is adopted.
[0100] The inorganic solid electrolyte may be contained alone or in combination of two or more.
[0101] When a solid electrolyte layer is formed, the solid electrolyte layer has a surface area (cm 2 The mass (mg) (weight per unit area) of the inorganic solid electrolyte is not particularly limited. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm 2 .
[0102] When the composition containing an inorganic solid electrolyte contains an active material described later, the total amount of the active material and the inorganic solid electrolyte is preferably within the above range regarding the weight per unit area of the inorganic solid electrolyte.
[0103] The content of the inorganic solid electrolyte in the composition containing the inorganic solid electrolyte is not particularly limited. From the viewpoint of adhesion and dispersibility, the solid content is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 90% by mass or more in 100% by mass of the solid component. As the upper limit, from the same viewpoint, it is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, and particularly preferably 99% by mass or less.
[0104] However, when the composition containing an inorganic solid electrolyte contains an active material described below, the content of the inorganic solid electrolyte in the composition containing an inorganic solid electrolyte is preferably a total content of the active material and the inorganic solid electrolyte within the above range.
[0105] In the present invention, the solid content refers to the components that do not disappear when the composition containing the inorganic solid electrolyte is dried at 150° C. for 6 hours under a nitrogen atmosphere at a pressure of 1 mmHg. Typically, it refers to the components other than the dispersion medium described below.
[0106] <Compound (SA)>
[0107] The inorganic solid electrolyte-containing composition of the present invention contains, as specific compounds (SA), any one or more compounds among the following (A) to (C).
[0108] (A): A compound represented by the formula (1) described below
[0109] (B): having at least one functional group among the functional groups included in the following functional group group (I), perfluoropolyether, polychlorotrifluoroethylene, polytetrafluoroethylene
[0110] (C): an organopolysiloxane having at least one functional group among the functional groups included in the following functional group group (I)
[0111] In the present invention, for convenience, the compounds included in the above-mentioned (A), (B) or (C) may be collectively referred to as compound group (A), (B) or (C).
[0112] The compound (SA) contained in the composition containing an inorganic solid electrolyte of the present invention may be one or more, for example, 1 to 3. When containing multiple compounds, they may be selected from the same compound group (any one of (A) to (C)) or from different compound groups.
[0113] As described above, each of the following compounds (A) to (C) exhibits a common effect of suppressing the generation of voids caused by charge and discharge of an all-solid-state secondary battery by being used in combination with an inorganic solid electrolyte in a constituent layer. From the viewpoint of this excellent effect, compound (A) is preferred.
[0114] The functional group contained in the compound (SA) is at least one of the functional groups included in the following functional group group (I). The functional group included in the following group (I) has the property of interacting with inorganic solid electrolytes, active materials, and even conductive aids and adsorbing. The interaction is not particularly limited, for example, the effect based on hydrogen bonds, the effect based on ionic bonds caused by acid-base, the effect based on covalent bonds, the effect based on π-π interactions caused by aromatic rings, or the effect based on hydrophobic-hydrophobic interactions, etc., can be cited. In the case where these functional groups interact, the chemical structure of the functional group may change or may not change. For example, in the above-mentioned π-π interactions, the functional group usually does not change and maintains the same structure. On the other hand, in the interaction based on covalent bonds, etc., it is usually an anion (functional group changes) from which active hydrogen such as carboxylic acid groups is detached and bonded to solid particles.
[0115] The number of functional groups possessed by one molecule of the compound is not particularly limited as long as it is 1 or more, and can be appropriately set. For example, the number of functional groups possessed by compound (A) can be set to 1 to 6, and more preferably 1 or 2. The number of functional groups possessed by compound (B) and compound (C) cannot be uniquely determined by the polymer structure, and can be, for example, 1 to 100, and compound (B) preferably has 1 or 2.
[0116] <Functional group (I)>
[0117] Acidic group, group having basic nitrogen atom, amide group, urea group, urethane group, alkoxysilyl group, epoxy group, isocyanate group, hydroxyl group or (meth)acryloyloxy group
[0118] The acidic group is not particularly limited, and examples thereof include a carboxylic acid group (-COOH), a sulfonic acid group (sulfonic acid group: -SO3H), a phosphoric acid group (phosphorus group: -OPO(OH)2), a phosphonic acid group, and a phosphinic acid group, and a carboxylic acid group is preferred.
[0119] Examples of the group having a basic nitrogen atom include amino, pyridyl, imino and amidino (-C(=NR)-NR2). The amino group has the same meaning as the amino group of the substituent Z described below, but is preferably an unsubstituted amino group or an alkylamino group. The three Rs of the amidino group each represent a hydrogen atom or a substituent (e.g., a group selected from the substituent Z described below).
[0120] Examples of the ureido group include -NR 15 CONR 16 R 17 (Here, R 15 , R 16 and R 17 represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 or more carbon atoms, or an aralkyl group having 7 or more carbon atoms. ) is a preferred example. As the ureido group, more preferably -NR 15 CONHR 17 (Here, R 15 and R 17 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 or more carbon atoms, or an aralkyl group having 7 or more carbon atoms. ), and -NHCONHR is particularly preferred. 17 (Here, R 17 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 or more carbon atoms, or an aralkyl group having 7 or more carbon atoms. ).
[0121] Examples of the carbamate group include -NHCOOR 18 、-NR 19 COOR 20 ,-OCONHR21 、-OCONR 22 R 23 (Here, R 18 , R 19 , R 20 , R 21 , R 22 and R 23 represents an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 or more carbon atoms, or an aralkyl group having 7 or more carbon atoms. ) and the like, and a group containing at least an imino group and a carbonyl group are preferred examples. As a carbamate group, -NHCOOR 18 ,-OCONHR 21 (Here, R 18 , R 21 represents an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 or more carbon atoms, an aralkyl group having 7 or more carbon atoms, etc., and -NHCOOR is particularly preferred. 18 ,-OCONHR 21 (Here, R 18 , R 21 represents an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 or more carbon atoms, an aralkyl group having 7 or more carbon atoms. ) and the like.
[0122] The amide group is not particularly limited, and examples thereof include -CONR 16 R 17 、-NR 15 -COR 18 (R 15 ~R 18 As described above. ) and the like, a group containing a carbonyl group and an amino group or an imino group is a preferred example. As an amide group, -NR 15 -COR 18 , more preferably -NHCOR 18 .
[0123] The alkoxysilyl group is not particularly limited, and examples thereof include mono-, di-, or tri-alkoxysilyl groups, preferably an alkoxysilyl group having 1 to 20 carbon atoms, and more preferably an alkoxysilyl group having 1 to 6 carbon atoms. Examples thereof include a methoxysilyl group, an ethoxysilyl group, a tert-butoxysilyl group, a cyclohexylsilyl group, and the groups exemplified in the substituent Z described later.
[0124] Examples of the (meth)acryloyloxy group include an acryloyloxy group and a methacryloyloxy group.
[0125] Acidic groups, groups having basic nitrogen atoms, hydroxyl groups, and the like can form salts.
[0126] The functional group possessed by the compound (SA) is preferably an acidic group, an alkoxysilyl group, an amide group, a urea group, a urethane group or an epoxy group, and is more preferably an acidic group.
[0127] The compound (A) is a compound represented by the following (1).
[0128] Formula (1) RAX
[0129] In formula (1), R represents an aliphatic hydrocarbon group having 6 or more carbon atoms and not having fluorine atoms (wherein, excluding a steroid ring structure), or a group comprising a fluorinated hydrocarbon group and a hydrocarbon group not having fluorine atoms. A represents a divalent linking group not containing an aromatic ring structure. X represents a functional group represented by the above functional group group (I).
[0130] R may be any of a form in which an aliphatic hydrocarbon group having 6 or more carbon atoms and not having fluorine atoms (excluding a steroid ring structure) is used (for convenience, referred to as the first form) and a form in which a group is used that includes a fluorinated hydrocarbon group and a hydrocarbon group not having fluorine atoms (for convenience, referred to as the second form).
[0131] In the first embodiment, R is an aliphatic hydrocarbon group. Thus, in the constituent layer, the interaction of the solid particles adsorbed by the compound (SA) with other solid particles existing in the vicinity thereof is reduced, and the frictional resistance between the solid particles can be reduced.
[0132] The aliphatic hydrocarbon group that can be used as R is not particularly limited, and may be an aliphatic saturated hydrocarbon group (alkyl group) or an aliphatic unsaturated hydrocarbon group (alkenyl group, alkynyl group). Among them, an alkyl group or an alkenyl group is preferred, and an alkyl group is more preferred.
[0133] And, aliphatic hydrocarbon group can be straight chain, branched or cyclic, and can partially contain cyclic structure.Wherein, this aliphatic hydrocarbon group does not contain the steroid ring structure (steroid skeleton) shown below.Not containing steroid ring structure means that aliphatic hydrocarbon group does not contain steroid ring structure in its structure, and then aliphatic hydrocarbon group itself is not the group of steroid ring structure.Aliphatic hydrocarbon group preferably does not contain cyclic structure, more preferably acyclic hydrocarbon group (straight chain or branched hydrocarbon group).As the mode that aliphatic hydrocarbon group does not contain cyclic structure, the mode that does not contain condensed ring structure, preferably more than 2 rings, more preferably more than 3 rings condensed ring structure can also be cited.This condensed ring structure can be aliphatic or aromatic.
[0134] From the viewpoint of reducing frictional resistance to solid particles, the aliphatic hydrocarbon group is preferably linear or branched, and more preferably linear.
[0135] [Chemical formula 1]
[0136]
[0137] The number of carbon atoms in the aliphatic hydrocarbon group is 6 or more, and from the viewpoint of reducing the friction resistance of the solid particles and the cycle characteristics, it is preferably 8 or more, more preferably 12 or more, and further preferably 18 or more. On the other hand, the upper limit of the number of carbon atoms is not particularly limited, but is preferably 30 or less, more preferably 25 or less, and further preferably 22 or less.
[0138] The number of carbon atoms of an aliphatic hydrocarbon group refers to the number of carbon atoms constituting the aliphatic hydrocarbon group, and when the aliphatic hydrocarbon group has a substituent, the number of carbon atoms constituting the substituent is not included. Among them, when the aliphatic hydrocarbon group is a branched hydrocarbon group, the number of carbon atoms constituting the branch is included (for example, in the case of 2-ethylhexyl, the number of carbon atoms is 8.).
[0139] The aliphatic hydrocarbon group may have a substituent, but does not have a fluorine atom and a steroid ring structure as a substituent. The substituent that the aliphatic hydrocarbon group may have is not particularly limited as long as it does not impair the effect of the present invention. For example, the substituent Z described below can be cited, preferably a group other than the functional group included in the functional group group (I) and a group other than the aryl group. That is, it is preferred that the aliphatic hydrocarbon group does not have a functional group, an aryl group, or a group containing these as a substituent.
[0140] In the second form, as a group that can be used as R and includes a fluorinated hydrocarbon group and a hydrocarbon group without fluorine atoms, there can be cited a group consisting of a fluorinated hydrocarbon group and a hydrocarbon group without fluorine atoms, and a group further comprising other groups other than these groups (i.e., other groups other than the fluorinated hydrocarbon group and the hydrocarbon group without fluorine atoms). Other groups are usually bonded between the fluorinated hydrocarbon group and the hydrocarbon group without fluorine atoms. As other groups, there is no particular limitation, and a connecting group that can be used as A described later can be cited. In the present invention, it is preferably a group consisting of a fluorinated hydrocarbon group and a hydrocarbon group without fluorine atoms.
[0141] The hydrocarbon group before fluorination and the hydrocarbon group without fluorine atoms constituting the fluorinated hydrocarbon group are not particularly limited, and may be an aromatic hydrocarbon group, but is preferably an aliphatic hydrocarbon group. This can reduce the frictional resistance of the solid particles.
[0142] The aliphatic hydrocarbon group is not particularly limited and may be an aliphatic saturated hydrocarbon group or an aliphatic unsaturated hydrocarbon group. Among them, an alkyl group or an alkenyl group is preferred, and an alkyl group is more preferred. In addition, the aliphatic hydrocarbon group may be linear, branched or cyclic, and may also partially contain a cyclic structure, but is preferably linear or branched, and more preferably linear. The aliphatic hydrocarbon group in the second form may contain a steroid ring structure.
[0143] The fluorinated hydrocarbon group in the second form is a fluorinated hydrocarbon group, and the number of carbon atoms is not particularly limited. The number of carbon atoms of the fluorinated hydrocarbon group can be set to 1 or more, for example, and from the perspective of reducing the friction resistance of the solid particles, reducing the resistance and the cycle characteristics, it is preferably 2 or more, more preferably 4 or more, and further preferably 5 or more. On the other hand, the upper limit of the number of carbon atoms is not particularly limited, and is preferably 20 or less, more preferably 15 or less, and further preferably 8 or less.
[0144] In the fluorinated hydrocarbon group, all hydrogen atoms possessed by the hydrocarbon group before fluorination can be substituted by fluorine atoms (perfluoro hydrocarbon group), or a part of it can be substituted by fluorine atoms. In the present invention, from the viewpoint of being able to effectively reduce the friction resistance of solid particles, perfluoro hydrocarbon group is preferred. In addition, when a part of hydrogen atoms is substituted by fluorine atoms, the remaining hydrogen atoms can be substituted by substituents other than fluorine atoms.
[0145] The hydrocarbon group without fluorine atoms in the second form is a hydrocarbon group other than a fluorinated hydrocarbon group, and may have a substituent, preferably a hydrocarbon group without a substituent (unsubstituted hydrocarbon group). The number of carbon atoms of the hydrocarbon group without fluorine atoms can be set to 1 or more, for example, from the perspective of reducing the friction resistance of the solid particles, reducing the resistance and the cycle characteristics, preferably 2 or more. On the other hand, the upper limit of the number of carbon atoms is not particularly limited, preferably 20 or less, more preferably 10 or less, and further preferably 6 or less.
[0146] The combination of the fluorinated hydrocarbon group and the hydrocarbon group without fluorine atoms in the second form is not particularly limited, and the combination of the above-mentioned preferred groups can be mentioned. Among them, the hydrocarbon group constituting the fluorinated hydrocarbon group and the hydrocarbon group without fluorine atoms are preferably both aliphatic hydrocarbon groups, more preferably alkyl groups, further preferably linear or branched alkyl groups, and particularly preferably linear alkyl groups.
[0147] The bonding method of the fluorinated hydrocarbon group and the hydrocarbon group without fluorine atoms in the second form is not particularly limited, and the side chain of one of the hydrocarbon groups may be bonded by another hydrocarbon group (for example, forming a branched hydrocarbon group as a whole), preferably in a straight chain (preferably forming a straight chain hydrocarbon group as a whole). In addition, any hydrocarbon group may be bonded to the linking group A of the above formula (1), but from the viewpoint of reducing the friction resistance of the solid particles, it is preferred that the hydrocarbon group without fluorine atoms is bonded to the linking group A, and the fluorinated hydrocarbon group becomes a terminal (free).
[0148] The total number of carbon atoms of the group including the fluorinated hydrocarbon group and the hydrocarbon group not having fluorine atoms is appropriately determined within the total range of the number of carbon atoms that the fluorinated hydrocarbon group and the hydrocarbon group not having fluorine atoms can adopt, and is preferably the same as the range of the number of carbon atoms of the aliphatic hydrocarbon group in the first form. In the present invention, the above-mentioned total number of carbon atoms has the same meaning as the number of carbon atoms of the aliphatic hydrocarbon group in the first form, and does not include the number of carbon atoms constituting the substituent.
[0149] In the present invention, the hydrocarbon group may contain one or more heteroatoms (atoms other than carbon atoms and hydrogen atoms, such as oxygen atoms, sulfur atoms, nitrogen atoms, and silicon atoms) within its molecular chain, but not containing one or more heteroatoms is one of the preferred aspects.
[0150] A in the formula (1) represents a divalent linking group not including an aromatic ring structure, and is preferably an aliphatic group.
[0151] The linking group that can be used as A is not particularly limited, and examples thereof include alkylene groups (preferably having 1 to 20 carbon atoms, more preferably 1 to 12, and even more preferably 1 to 6 carbon atoms), alkenylene groups (preferably having 2 to 18 carbon atoms, more preferably 2 to 10, and even more preferably 2 to 6 carbon atoms), oxygen atoms, sulfur atoms, imino groups (-NR N -), carbonyl, phosphate linking group (-OP(OH)(O)-O-), phosphonic acid linking group (-P(OH)(O)-O-), or groups related to combinations thereof, etc.
[0152] The alkylene group and alkenylene group that can be used as the linking group can be any one of straight chain, branched chain or cyclic, but from the viewpoint of reducing the friction resistance of the solid particles, the alkylene group is preferably straight chain or branched chain, and the alkenylene group is preferably straight chain. As the cyclic alkylene group, cyclohexane ring group and norbornene ring group can be mentioned, and as the cyclic alkenylene group, cyclohexene ring group and norbornene ring group can be mentioned.
[0153] As the group involved in the combination of the above-mentioned groups, it is preferred that an alkylene group, an alkenylene group, a carbonyl group, an oxygen atom, a sulfur atom and an imino group are combined, and it is more preferred that an alkylene group, an alkenylene group, a carbonyl group, an oxygen atom and an imino group are combined, and it is further preferred that a group comprising a -CO-O- group is combined, and it is particularly preferred that a group comprising a -CO-O- group is combined with an alkylene group or an alkenylene group. In the group comprising a -CO-O- group, it is preferred that the -CO-O- group is bonded to R in formula (1), and it is more preferred that the oxygen atom in the -CO-O- group is bonded to R in formula (1). As the group comprising a -CO-O- group, the groups shown in the compounds used in the embodiments can be cited, but are not limited to these.
[0154] In the present invention, the total number of atoms constituting the linking group is preferably 1 to 36, more preferably 1 to 24, further preferably 1 to 12, and particularly preferably 1 to 6. The number of connecting atoms of the linking group is preferably 10 or less, more preferably 8 or less. The lower limit is 1 or more. The above-mentioned number of connecting atoms refers to the minimum number of atoms connecting R and X of formula (1). For example, in the case of a linking group composed of a cyclohexane ring and a -CO-O- group of compound A-08 used in the examples, the number of atoms constituting the linking group becomes 19, but the number of connecting atoms becomes 4.
[0155] The linking group that can be used as A is preferably an alkylene group, an oxygen atom, or a group composed of a -CO-O- group and an alkylene group or an alkenylene group. From the viewpoint of reducing the friction resistance of the solid particles, an alkylene group is more preferred.
[0156] In formula (1), when the RA-group is a single group (excluding aralkyl), the minimum unit of the above-mentioned linking group contained in the single group is set to A, and the remainder is set to R. For example, when the RA-group is an alkyl group as a whole (undecyl in compound A-01 used in the example), A is set to methylene (the minimum unit of alkylene as a linking group), and the remaining group (decyl in compound A-01) is set to R.
[0157] The linking group that can be used as A may have a substituent, but preferably has no substituent. The substituent that A may have includes a substituent Z other than the functional group selected from the functional group group (I) and other than the group that can be used as R.
[0158] X in formula (1) represents a functional group included in the functional group group (I). The functional group is as described above, and the preferred embodiments are also the same.
[0159] The compound (A) may have a substituent. The substituent is not particularly limited as long as it does not impair the effects of the present invention, and examples thereof include the substituent Z described below, preferably a group other than the functional group included in the functional group group (I) and a group other than the aryl group.
[0160] The compound (A) is preferably a low molecular weight compound, and the molecular weight thereof can be appropriately determined. The molecular weight can be, for example, 150 to 1,000.
[0161] The compound (B) is perfluoropolyether, polychlorotrifluoroethylene or polytetrafluoroethylene, preferably perfluoropolyether.
[0162] There is no particular limitation on the perfluoropolyether, and polymers having alkylene oxides, aryl oxides, etc. as constituent components can be cited. As long as compound (B) is a polymer having a fluorinated constituent component, there is no particular limitation on the other components. For example, the number of carbon atoms of the alkylene group in the alkylene oxide is not particularly limited, and can be, for example, 1 to 10, preferably 1 to 6. The number of carbon atoms of the arylene group in the arylene oxide is not particularly limited, and can be, for example, 6 to 10.
[0163] The compound (B) has a functional group selected from the functional group group (I) above. The functional group may be introduced into any of the constituent components forming the compound (B), but is preferably introduced into the main chain terminal of the polymer chain.
[0164] The number average molecular weight of the compound (B) is not particularly limited, and can be, for example, 1,000 to 50,000.
[0165] As perfluoropolyether, for example, Fluorolink (registered trademark) series (PFPE, manufactured by Solvey) and perfluoropolyether manufactured by MORESCO can be cited. As polychlorotrifluoroethylene, for example, Neoflon PCTFE M series (manufactured by DAIKIN INDUSTRIES, LTD.) can be cited. As polytetrafluoroethylene, Polyflon PTFE series (manufactured by DAIKIN INDUSTRIES, LTD.) and polytetrafluoroethylene manufactured by Shamrock Technologies can be cited.
[0166] The organopolysiloxane of the compound (C) is not particularly limited, and is a polymer having a siloxane structure and having at least one functional group among the functional groups included in the functional group group (I).
[0167] The siloxane structure of the organopolysiloxane includes, for example, -Si(R S 2) A structural unit represented by -O-. In this structural unit, R S represents a hydrogen atom or a substituent. The substituent is not particularly limited, and examples thereof include hydroxyl, alkyl (preferably having 1 to 12 carbon atoms, more preferably 1 to 6, and particularly preferably 1 to 3), alkenyl (preferably having 2 to 12 carbon atoms, more preferably 2 to 6, and particularly preferably 2 or 3), alkoxy (preferably having 1 to 24 carbon atoms, more preferably 1 to 12, further preferably 1 to 6, and particularly preferably 1 to 3), aryl (preferably having 6 to 22 carbon atoms, more preferably 6 to 14, and particularly preferably 6 to 10), aryloxy (preferably having 6 to 22 carbon atoms, more preferably 6 to 14, and particularly preferably 6 to 10), aralkyl (preferably having 7 to 23 carbon atoms, more preferably 7 to 15, and particularly preferably 7 to 11), and the substituent ZC in the formula (2) described later or -R11 Among them, an alkyl group having 1 to 3 carbon atoms, a phenyl group, a substituent ZC, or a group represented by -R 11 The group represented by -X is more preferably an alkyl group having 1 to 3 carbon atoms or a 11 -A group represented by X.
[0168] The siloxane structure is preferably a polymer chain having two or more of the above structural units, and the degree of polymerization of all structural units forming the polymer chain is not particularly limited, preferably 1 to 1000, more preferably 1 to 500, and particularly preferably 1 to 200. The number average molecular weight of the above polymer chain is not particularly limited, and is preferably 400 or more, more preferably 800 or more, and further preferably 2,000 or more. There is no particular restriction on the upper limit, but it is preferably 500,000 or less, more preferably 100,000 or less, and particularly preferably 50,000 or less. The number average molecular weight of the polymer chain can be measured as a number average molecular weight converted to standard polystyrene as described later.
[0169] The organopolysiloxane is preferably a polymer represented by the following formula (2).
[0170] [Chemical formula 2]
[0171]
[0172] In formula (2), R 15 represents an alkyl group or an aryl group, preferably an alkyl group. 15 The alkyl and aryl groups used are respectively related to the above structural units as R S The alkyl and aryl groups used have the same meanings and the same preferred ranges. 15 The two R atoms bonded to the same silicon atom are preferably methyl. 15 They may be the same or different, and are preferably methyl.
[0173] R 16 represents an alkyl group or an aryl group, preferably an alkyl group. The two R 16 They may be the same or different. 16 The alkyl and aryl groups used are respectively related to the above structural units as R S The alkyl and aryl groups used have the same meanings and the same preferred ranges.
[0174] R 11 Represents a linking group. 11The linking group used is not particularly limited, and is preferably an alkylene group having 1 to 30 carbon atoms, a cycloalkylene group having 3 to 12 carbon atoms, an arylene group having 6 to 24 carbon atoms, a heteroarylene group having 3 to 12 carbon atoms, an ether group (-O-), a thioether group (-S-), a phosphine group (-PR-: R is a hydrogen atom or an alkyl group having 1 to 6 carbon atoms), a silylene group (-SiR S1 R S2 -:R S1 , R S2 is a hydrogen atom or an alkyl group having 1 to 6 carbon atoms), a carbonyl group, an imino group (-NR N -:R N The present invention is a linking group which is a hydrogen atom, an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms), or a linking group which is a combination of two or more thereof (preferably 2 to 10). Among them, an alkylene group, an imino group, an ether group, a thioether group or a carbonyl group, or a linking group which is a combination of two or more thereof (preferably 2 to 5) is preferred.
[0175] X has the same meaning as X in the above formula (1).
[0176] ZC represents a group represented by the following formula (Z).
[0177] [Chemical formula 3]
[0178]
[0179] In formula (Z), R 17 and R 18 represents an alkyl group or an aryl group respectively. 17 and R 18 The alkyl and aryl groups used are respectively connected to the siloxane structure as R S The alkyl and aryl groups used have the same meanings and the same preferred ranges. 17 and R 18 Can be the same or different. 19 represents an unsubstituted alkyl group having 1 to 4 carbon atoms. y2 is an integer of 1 to 100, preferably an integer of 1 to 50, and more preferably an integer of 1 to 20.
[0180] In formula (2), x1, x2 and x3 are each an integer greater than or equal to 0.
[0181] x1 is preferably an integer of 0-50, more preferably an integer of 0-20.
[0182] x2 is preferably an integer of 0-50, more preferably an integer of 0-20.
[0183] x3 is preferably an integer of 1-500, more preferably an integer of 1-200.
[0184] x4 is preferably an integer of 0-200, more preferably an integer of 0-100, and even more preferably an integer of 0-30.
[0185] x1, x2, x3 and x4 are an integer of 1-500 in total, preferably an integer of 1-200, and more preferably an integer of 1-100.
[0186] When x1 and x3 are each an integer greater than 2, in Formula 2, two ZC or R bonded to the same silicon atom 15 May be the same as or different from each other.
[0187] y1 is an integer of 1-30, preferably an integer of 1-20, and more preferably an integer of 1-10.
[0188] In formula (2), Y represents the above-R 11 -X represents a group or R 16 , the two Ys can be the same or different.
[0189] The polymer represented by formula (2) has at least one -R 11 -X represented group, for example, in formula (2), X4 and y1 are at least 1, and at least one of the two Ys is represented by -R 11 That is, when x4 is 0, any one of the two Ys represents a group represented by -R 11 -X, or when both Y are R 16 When x4 and y1 are integers greater than 1.
[0190] The above compounds (A) to (C) may be commercially available products or may be appropriately synthesized. The synthesis method is not particularly limited, and a known method may be selected and the conditions may be appropriately set.
[0191] -Substituent Z-
[0192] Examples thereof include alkyl groups (preferably alkyl groups having 1 to 20 carbon atoms, for example, methyl, ethyl, isopropyl, tert-butyl, pentyl, heptyl, 1-ethylpentyl, benzyl, 2-ethoxyethyl, 1-carboxymethyl, etc.), alkenyl groups (preferably alkenyl groups having 2 to 20 carbon atoms, for example, vinyl, allyl, oleyl, etc.), alkynyl groups (preferably alkynyl groups having 2 to 20 carbon atoms, for example, ethynyl, butadiynyl, phenylethynyl, etc.), and cycloalkyl groups (preferably cycloalkyl groups having 3 to 20 carbon atoms, for example, cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, etc. In the present specification, the term "alkyl" generally refers to a group containing Cycloalkyl, but it is described separately here. ), aryl (preferably an aryl group having 6 to 26 carbon atoms, for example, phenyl, 1-naphthyl, 4-methoxyphenyl, 2-chlorophenyl, 3-methylphenyl, etc.), aralkyl (preferably an aralkyl group having 7 to 23 carbon atoms, for example, benzyl, phenethyl, etc.), heterocyclic group (preferably a heterocyclic group having 2 to 20 carbon atoms, more preferably a 5- or 6-membered heterocyclic group having at least one oxygen atom, sulfur atom, or nitrogen atom. The heterocyclic group includes an aromatic heterocyclic group and an aliphatic heterocyclic group. For example, a tetrahydropyranyl ring group, a tetrahydrofuranyl ring group, a 2-pyridyl group, a 4-pyridyl group, a 2-imidazolyl group , 2-benzimidazolyl, 2-thiazolyl, 2-oxazolyl, pyrrolidonyl, etc.), alkoxy (preferably alkoxy having 1 to 20 carbon atoms, for example, methoxy, ethoxy, isopropoxy, benzyloxy, etc.), aryloxy (preferably aryloxy having 6 to 26 carbon atoms, for example, phenoxy, 1-naphthyloxy, 3-methylphenoxy, 4-methoxyphenoxy, etc., and the term "aryloxy" in this specification includes aroyloxy), heterocyclic oxy (a group in which an -O- group is bonded to the above heterocyclic group), alkoxycarbonyl (preferably alkoxycarbonyl having 2 to 20 carbon atoms, for example, ethoxycarbonyl, 2-ethylhexyl oxycarbonyl, dodecyloxycarbonyl, etc.), aryloxycarbonyl (preferably aryloxycarbonyl having 6 to 26 carbon atoms, for example, phenoxycarbonyl, 1-naphthyloxycarbonyl, 3-methylphenoxycarbonyl, 4-methoxyphenoxycarbonyl, etc.), heterocyclic oxycarbonyl (a group in which a -O-CO- group is bonded to the above heterocyclic group), amino (preferably amino, alkylamino, arylamino having 0 to 20 carbon atoms, for example, amino (-NH2), N,N-dimethylamino, N,N-diethylamino, N-ethylamino, anilino, etc.), sulfamoyl (preferably sulfamoyl having 0 to 20 carbon atoms, for example, N,N-dimethylsulfamoyl, N-phenylsulfamoyl, etc.), acyl (including alkylcarbonyl, alkenylcarbonyl, alkynylcarbonyl, arylcarbonyl, heterocyclic carbonyl, preferably acyl having 1 to 20 carbon atoms, for example, acetyl, propionyl, butyryl, octanoyl, hexadecanoyl, acryloyl, methacryloyl, crotonyl, benzoyl, naphthoyl, nicotinoyl, etc.), acyloxy (including alkylcarbonyloxy, alkenylcarbonyloxy, alkynylcarbonyloxy, arylcarbonyloxy, heterocyclic carbonyloxy, preferably acyloxy having 1 to 20 carbon atoms, for example, acetyloxy, propionyloxy, butyryloxy, octanoyloxy , hexadecanoyloxy, acryloyloxy, methacryloyloxy, crotonyloxy, benzoyloxy, naphthoyloxy, nicotinyloxy, etc.), aryloxy (preferably aryloxy having 7 to 23 carbon atoms, for example, benzoyloxy, etc.), carbamoyl (preferably carbamoyl having 1 to 20 carbon atoms, for example, N,N-dimethylcarbamoyl, N-phenylcarbamoyl, etc.), acylamino (preferably acylamino having 1 to 20 carbon atoms, for example, acetylamino, benzylamino, etc.), alkylthio (preferably alkylthio having 1 to 20 carbon atoms, for example, methylthio, ethylthio, isopropylthio , benzylthio, etc.), arylthio (preferably arylthio having 6 to 26 carbon atoms, for example, phenylthio, 1-naphthylthio, 3-methylphenylthio, 4-methoxyphenylthio, etc.), heterocyclic thio (a group in which -S- is bonded to the above heterocyclic group), alkylsulfonyl (preferably alkylsulfonyl having 1 to 20 carbon atoms, for example, methylsulfonyl, ethylsulfonyl, etc.), arylsulfonyl (preferably arylsulfonyl having 6 to 22 carbon atoms, for example, benzylsulfonyl, etc.), alkylsilyl (preferably alkylsilyl having 1 to 20 carbon atoms, for example, monomethylsilyl, dimethylsilyl , trimethylsilyl, triethylsilyl, etc.), arylsilyl (preferably arylsilyl having 6 to 42 carbon atoms, for example, triphenylsilyl, etc.), alkoxysilyl (preferably alkoxysilyl having 1 to 20 carbon atoms, for example, monomethoxysilyl, dimethoxysilyl, trimethoxysilyl, triethoxysilyl, etc.), aryloxysilyl (preferably aryloxysilyl having 6 to 42 carbon atoms, for example, triphenoxysilyl, etc.), phosphoryl (preferably phosphate having 0 to 20 carbon atoms, for example, -OP(=O)(R, P ) 2), phosphono group (preferably a phosphono group having 0 to 20 carbon atoms, for example, -P(=O)(R P ) 2), phosphinyl group (preferably a phosphinyl group having 0 to 20 carbon atoms, for example, -P(R P ) 2), phosphonic acid group (preferably a phosphonic acid group having 0 to 20 carbon atoms, for example, -PO(OR P ) 2) sulfo group (sulfonic acid group), carboxyl group, hydroxyl group, sulfanyl group, cyano group, halogen atom (for example, fluorine atom, chlorine atom, bromine atom, iodine atom, etc.). Pis a hydrogen atom or a substituent (preferably a group selected from the substituent Z).
[0193] Furthermore, each group listed in these substituents Z may be further substituted by the substituents Z described above.
[0194] The above-mentioned alkyl group, alkylene group, alkenyl group, alkenylene group, alkynyl group and / or alkynylene group etc. may be cyclic or chain-shaped, and may be straight-chain or branched.
[0195] The content of the compound (SA) in the composition containing the inorganic solid electrolyte is not particularly limited. From the viewpoint of reducing the friction resistance of the solid particles, the solid content is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and particularly preferably 0.4% by mass or more in 100% by mass of the solid component. As the upper limit, from the viewpoint of reducing the battery resistance, it is preferably 10% by mass or less, more preferably 4% by mass or less, further preferably 2.5% by mass or less, and particularly preferably 1.2% by mass or less.
[0196] In the composition containing an inorganic solid electrolyte of the present invention, the ratio of the content of the inorganic solid electrolyte [SE] in 100% by mass of the solid component to the total content of the compound (SA) [SA]: [SA] / [SE] is not particularly limited. From the viewpoint of reducing the frictional resistance of the solid particles, lowering the resistance and improving the cycle characteristics, it is preferably 0.0003 to 0.11. From the viewpoint of further reducing the frictional resistance of the solid particles and being able to take into account both lowering the resistance and improving the cycle characteristics at a high level, it is more preferably 0.003 to 0.05, further preferably 0.007 to 0.05, and particularly preferably 0.01 to 0.03.
[0197] When the composition containing an inorganic solid electrolyte of the present invention contains the following polymer binder, the ratio of the content [BR] of the polymer binder to the total content [SA] of the compound (SA) in 100% by mass of the solid component of the composition containing an inorganic solid electrolyte: [BR] / [SA] is not particularly limited. From the viewpoint of reducing the frictional resistance of the solid particles, lowering the resistance and improving the cycle characteristics, it is preferably 0.05 to 15. From the viewpoint of further reducing the frictional resistance of the solid particles and being able to achieve both lowering the resistance and improving the cycle characteristics at a high level, it is more preferably 0.1 to 10, further preferably 0.2 to 5, and particularly preferably 0.8 to 5.
[0198] <Polymer Binder>
[0199] The inorganic solid electrolyte-containing composition of the present invention preferably contains a polymer binder. By containing a polymer binder, the binding properties of the solid particles can be improved, and the cycle characteristics and the like can be improved.
[0200] There is no particular limitation on the polymer forming the polymer binder, and various polymers commonly used in the constituent layers of all-solid-state secondary batteries can be cited. For example, step-polymerization (polycondensation, polyaddition or addition condensation) polymers such as polyurethane, polyurea, polyamide, polyimide, polyester, polyether, polycarbonate, and further chain polymerization polymers such as fluorine-based polymers (fluorine-containing polymers), hydrocarbon-based polymers, ethylene-based polymers, and (meth)acrylic polymers can be cited.
[0201] Examples of polymers of polyurethane, polyurea, polyamide, and polyimide that can be used as step-polymerization polymers include polymers having hard segments and soft segments described in Japanese Patent Application Publication No. 2015-088480, and polymers described in International Publication No. 2018 / 147051, International Publication No. 2018 / 020827, and International Publication No. 2015 / 046313.
[0202] As fluorine-containing polymers, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), copolymers of polyvinylidene fluoride and hexafluoropropylene (PVdF-HFP), copolymers of polyvinylidene fluoride, hexafluoropropylene and tetrafluoroethylene (PVdF-HFP-TFE) can be cited. In PVdF-HFP, the copolymerization ratio of PVdF to HFP [PVdF:HFP] (mass ratio) is not particularly limited, and is preferably 9:1 to 5:5, and more preferably 9:1 to 7:3. In PVdF-HFP-TFE, the copolymerization ratio of PVdF, HFP and TFE [PVdF:HFP:TFE] (mass ratio) is not particularly limited, and is preferably 20 to 60:10 to 40:5 to 30.
[0203] As hydrocarbon polymers, for example, polyethylene, polypropylene, natural rubber, polybutadiene, polyisoprene, polystyrene, polystyrene butadiene copolymer, styrene thermoplastic elastomer, polybutene, acrylonitrile butadiene copolymer, or hydrogenated (hydrogenated) polymers thereof can be cited. As styrene thermoplastic elastomer or its hydrogenate, there is no particular limitation, for example, styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS), styrene-isobutylene-styrene block copolymer (SIBS), hydrogenated SIS, styrene-butadiene-styrene block copolymer (SBS), hydrogenated SBS, styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber (HSBR), and random copolymers corresponding to the above-mentioned block copolymers can be cited. In the present invention, the hydrocarbon-based polymer is preferred in that the polymer having no unsaturated group (such as 1,2-butadiene constituent component) bonded to the main chain can suppress the formation of chemical crosslinks.
[0204] As the ethylene polymer, for example, a polymer containing 50 mol% or more of ethylene monomers other than the (meth) acrylic acid compound (M1) can be mentioned. As the ethylene monomer, vinyl compounds described below can be mentioned. As the ethylene polymer, specifically, for example, polyvinyl alcohol, polyvinyl acetal, polyvinyl acetate or copolymers containing these can be mentioned.
[0205] The ethylene polymer preferably has, in addition to the constituents derived from the ethylene monomer, constituents derived from the (meth)acrylic acid compound (M1) that form the (meth)acrylic acid polymer described later, and further constituents (MM) derived from the macromonomer described later. The content of the constituents derived from the ethylene monomer is preferably the same as the content of the constituents derived from the (meth)acrylic acid compound (M1) in the (meth)acrylic acid polymer. The content of the constituents derived from the (meth)acrylic acid compound (M1) is not particularly limited as long as it is less than 50 mol% in the polymer, and is preferably 0 to 40 mol%, more preferably 5 to 35 mol%. The content of the constituent (MM) is preferably the same as that in the (meth)acrylic acid polymer.
[0206] As a (meth)acrylic polymer, it is preferred that a polymer is obtained by (co)polymerizing at least one (meth)acrylic compound (M1) selected from a (meth)acrylic compound, a (meth)acrylic ester compound, a (meth)acrylamide compound, and a (meth)acrylic nitrile compound. In addition, a (meth)acrylic polymer composed of a copolymer of a (meth)acrylic compound (M1) and other polymerizable compounds (M2) is also preferred. There is no particular limitation on other polymerizable compounds (M2), and vinyl compounds such as styrene compounds, vinyl naphthalene compounds, vinyl carbazole compounds, allyl compounds, vinyl ether compounds, vinyl ester compounds, and dialkyl itaconic acid compounds can be cited. As a vinyl compound, for example, the "vinyl monomer" described in Japanese Patent Gazette No. 2015-88486 can be cited.
[0207] In addition, a (meth)acrylic polymer having a constituent component (MM) derived from a macromonomer is also preferred. Examples of such a (meth)acrylic polymer include a polymer described in International Publication No. 2016 / 132872, which has a macromonomer having a mass average molecular weight of 1,000 or more incorporated as a side chain component and has at least one of the following functional group groups (b).
[0208] Functional group (b): carboxyl, sulfonic acid, phosphoric acid, phosphonic acid
[0209] In the (meth)acrylic polymer, the content of the constituent derived from the (meth)acrylic compound (M1) is preferably 50 mol% or more, and the content of the other polymerizable compound (M2) is not particularly limited, but can be, for example, 50 mol% or less, preferably less than 50 mol%. The content of the constituent (MM) is preferably 1 to 70 mass%.
[0210] The polymer binder is preferably polyurethane, a fluorine-based polymer or a hydrocarbon-based polymer, more preferably polyurethane, PVdF-HFP, SEBS, SBS, SBR or HSBR, further preferably polyurethane, PVdF-HFP or SEBS, and particularly preferably polyurethane or PVdF-HFP.
[0211] The main chain forming the step-wise polymerization polymer is not particularly limited, and is preferably a main chain formed by combining two or more (preferably 2 to 8, more preferably 2 to 4) constituent components represented by any one of the following formulas (I-1) to (I-4) or a main chain formed by step-polymerizing a carboxylic acid diester represented by the following formula (I-5) and a diamine compound introduced as a constituent component represented by the following formula (I-6). Examples of polymers having such a main chain include polyurethanes, polyureas, polyamides, polyimides, polyesters, and polycarbonates. The combination of constituent components can be appropriately selected depending on the type of polymer. Examples of the main chain composed of polycarbonate include a main chain having a carbonyl group at R P1 A constituent represented by the following formula (I-2) in which oxygen atoms are introduced into both ends of P1 The main chain of the constituent represented by the following formula (I-2) and the constituent represented by the following formula (I-3) using the constituent represented by the following formula. One constituent in the combination of constituents refers to the number of types of constituents represented by any of the following formulas, and even if there are two constituents represented by one of the following formulas, it will not be interpreted as two constituents.
[0212] [Chemical formula 4]
[0213]
[0214] In the formula, R P1 and R P2 Respectively represent molecular chains with a molecular weight or mass average molecular weight of 20 or more and 200,000 or less. The molecular weight of the molecular chain cannot be uniquely determined because it depends on its type, etc., for example, it is preferably 30 or more, more preferably 50 or more, further preferably 100 or more, and particularly preferably 150 or more. As an upper limit, it is preferably 100,000 or less, more preferably 10,000 or less. The molecular weight of the molecular chain is measured for the raw material compound before being incorporated into the main chain of the polymer.
[0215] R P1 and R P2 The molecular chain that can be used is not particularly limited, and is preferably a hydrocarbon chain, a polyalkylene oxide chain, a polycarbonate chain or a polyester chain, more preferably a hydrocarbon chain or a polyalkylene oxide chain, and further preferably a hydrocarbon chain, a polyethylene oxide chain or a polypropylene oxide chain.
[0216] R P1 and R P2The hydrocarbon chain that can be used refers to a hydrocarbon chain composed of carbon atoms and hydrogen atoms, and more specifically, refers to a structure formed by the separation of at least two atoms (e.g., hydrogen atoms) or groups (e.g., methyl groups) in a compound composed of carbon atoms and hydrogen atoms. However, in the present invention, for example, as the hydrocarbon group represented by the following formula (M2), the hydrocarbon chain also includes a chain having a group containing an oxygen atom, a sulfur atom or a nitrogen atom in the chain. The terminal group that may be present at the end of the hydrocarbon chain is not included in the hydrocarbon chain. The hydrocarbon chain may have a carbon-carbon unsaturated bond, or may have a ring structure of an aliphatic ring and / or an aromatic ring. That is, the hydrocarbon chain may be a hydrocarbon chain composed of hydrocarbons selected from aliphatic hydrocarbons and aromatic hydrocarbons.
[0217] Such a hydrocarbon chain may be any hydrocarbon chain as long as it satisfies the above-mentioned molecular weight, and includes both hydrocarbon chains consisting of a low-molecular-weight hydrocarbon group and a hydrocarbon chain consisting of a hydrocarbon polymer (also referred to as a hydrocarbon polymer chain).
[0218] The low molecular weight hydrocarbon chain is a chain composed of a common (non-polymerizable) hydrocarbon group, and examples of the hydrocarbon group include aliphatic or aromatic hydrocarbon groups, and specifically, preferably an alkylene group (preferably having 1 to 12 carbon atoms, more preferably 1 to 6, and further preferably 1 to 3 carbon atoms), an arylene group (preferably having 6 to 22 carbon atoms, preferably 6 to 14, and more preferably 6 to 10 carbon atoms), or a group composed of a combination thereof. P2 The hydrocarbon group of the low molecular weight hydrocarbon chain that can be used is more preferably an alkylene group, more preferably an alkylene group having 2 to 6 carbon atoms, and particularly preferably an alkylene group having 2 or 3 carbon atoms. The hydrocarbon chain may have a polymer chain (eg, a (meth)acrylic acid polymer) as a substituent.
[0219] The aliphatic hydrocarbon group is not particularly limited, and examples thereof include hydrogen reduction products of aromatic hydrocarbon groups represented by the following formula (M2), partial structures possessed by known aliphatic diisocyanate compounds (e.g., groups composed of isophorone), etc. In addition, hydrocarbon groups possessed by the constituent components described below may also be mentioned.
[0220] Examples of the aromatic hydrocarbon group include hydrocarbon groups possessed by the constituent components described below, preferably an arylene group (for example, a group obtained by further removing one or more hydrogen atoms from an aryl group listed in the substituent Z described below, specifically a phenylene group, a tolylene group or a xylene group) or a hydrocarbon group represented by the following formula (M2).
[0221] [Chemical formula 5]
[0222]
[0223] In formula (M2), X represents a single bond, -CH2-, -C(CH3)2-, -SO2-, -S-, -CO- or -O-, and from the viewpoint of adhesion, is preferably -CH2- or -O-, and more preferably -CH2-. The alkylene group exemplified herein may be substituted by a substituent Z, preferably a halogen atom (more preferably a fluorine atom).
[0224] R M2 ~R M5 Each of R represents a hydrogen atom or a substituent, preferably a hydrogen atom. M2 ~R M5 The substituents that can be used are not particularly limited, and examples thereof include the substituent Z described below, and preferably include an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 1 to 20 carbon atoms, -OR M6 ,―N(R M6 )2. -SR M6 (R M6 represents a substituent, preferably an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 10 carbon atoms. ), a halogen atom (e.g., a fluorine atom, a chlorine atom, or a bromine atom). As -N(R M6 )2, for example, an alkylamino group (preferably having 1 to 20 carbon atoms, more preferably 1 to 6 carbon atoms) or an arylamino group (preferably having 6 to 40 carbon atoms, more preferably 6 to 20 carbon atoms).
[0225] The hydrocarbon polymer chain is a polymer chain formed by polymerizing polymerizable hydrocarbons (at least 2), and there is no particular limitation as long as it is a chain composed of a hydrocarbon polymer having a carbon number greater than that of the above-mentioned low molecular weight hydrocarbon chain, and is a chain containing a hydrocarbon polymer preferably composed of 30 or more, more preferably 50 or more carbon atoms. The upper limit of the number of carbon atoms constituting the hydrocarbon polymer is not particularly limited, and can be set to 3,000, for example. The hydrocarbon polymer chain is preferably a chain of a hydrocarbon polymer composed of aliphatic hydrocarbons whose main chain satisfies the above-mentioned number of carbon atoms, and is more preferably a chain containing a polymer (preferably an elastomer) composed of aliphatic saturated hydrocarbons or aliphatic unsaturated hydrocarbons. As polymers, specifically, diene polymers having double bonds on the main chain and non-diene polymers having no double bonds on the main chain can be cited. Examples of diene polymers include styrene-butadiene copolymers, styrene-vinyl-butadiene copolymers, copolymers of isobutylene and isoprene (preferably butyl rubber (IIR)), butadiene polymers, isoprene polymers, and vinyl-propylene-diene copolymers. Examples of non-diene polymers include olefin polymers such as vinyl-propylene copolymers and styrene-vinyl-propylene copolymers, and hydrogen-reduced products of the above diene polymers.
[0226] Can be used as R P1 and R P2The hydrocarbon chain used may have a substituent as described below, and preferably has an ether group or a carbonyl group or both. In particular, R P2 The hydrocarbon chain used preferably has an ether group or a carbonyl group or both (for example, a -CO-O- group, preferably a carboxyl group). The ether group and the carbonyl group preferably have atoms such as hydrogen atoms or substituents (for example, the substituent Z described below) at the ends.
[0227] The hydrocarbon forming the hydrocarbon chain preferably has a reactive group at its terminal, and more preferably has a terminal reactive group capable of polycondensation. The terminal reactive group capable of polycondensation or polyaddition forms a bond to R P1 or R P2 Examples of such terminal reactive groups include isocyanate, hydroxyl, carboxyl, amino and acid anhydride, among which hydroxyl is preferred.
[0228] As the hydrocarbon polymer having a terminal reactive group, for example, NISSO-PB series (manufactured by NIPPON SODA CO., LTD.), Claysol series (manufactured by TOMOE Engineering Co., Ltd.), PolyVEST-HT series (manufactured by EVONIK CO., LTD.), poly-bd series (manufactured by Idemitsu Kosan Co., Ltd.), poly-ip series (manufactured by Idemitsu Kosan Co., Ltd.), EPOL (manufactured by Idemitsu Kosan Co., Ltd.) and POLYTAIL series (manufactured by Mitsubishi Chemical Corporation) all of which are trade names can be preferably used.
[0229] As the polyalkylene oxide chain (polyalkylene oxide chain), a chain composed of a known polyalkyleneoxy group can be mentioned. The carbon number of the alkyleneoxy group in the polyalkylene oxide chain is preferably 1 to 10, more preferably 1 to 6, and further preferably 2 or 3 (polyethylene oxide chain or polypropylene oxide chain). The polyalkylene oxide chain may be a chain composed of one type of alkylene oxide group, or a chain composed of two or more types of alkylene oxide groups (for example, a chain composed of ethylene oxide and propylene oxide).
[0230] Examples of the polycarbonate chain or the polyester chain include chains composed of known polycarbonates or polyesters.
[0231] The polyalkyleneoxy chain, the polycarbonate chain or the polyester chain preferably has an alkyl group (preferably having 1 to 12 carbon atoms, more preferably 1 to 6 carbon atoms) at the terminal.
[0232] R P1 and RP2 The ends of the polyalkylene oxide chain, polycarbonate chain and polyester chain that can be used can be appropriately changed to P1 and R P2 The common chemical structure that can be incorporated into the constituents represented by the above formulae. For example, a polyalkyleneoxy chain is formed by removing the terminal oxygen atom as R of the above constituents. P1 or R P2 And merged.
[0233] The alkyl group contained in the molecular chain may have an ether group (-O-), a thioether group (-S-), a carbonyl group (>C=O), an imino group (>NR N : R N is a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms).
[0234] In the above formulas, R P1 and R P2 It is a divalent molecular chain, but at least one hydrogen atom is replaced by -NH-CO-, -CO-, -O-, -NH- or -N<, and it can become a trivalent or higher molecular chain.
[0235] R P1 Among the above molecular chains, hydrocarbon chains are preferred, low molecular weight hydrocarbon chains are more preferred, hydrocarbon chains composed of aliphatic or aromatic hydrocarbon groups are further preferred, and hydrocarbon chains composed of aromatic hydrocarbon groups are particularly preferred.
[0236] R P2 Among the above molecular chains, a low molecular weight hydrocarbon chain (more preferably an aliphatic hydrocarbon group) or a molecular chain other than a low molecular weight hydrocarbon chain is preferred, and a mode including a low molecular weight hydrocarbon chain and a molecular chain other than a low molecular weight hydrocarbon chain is more preferred. In this mode, the constituent represented by any one of formula (I-3), formula (I-4) and formula (I-6) contains R P2 It is a low molecular weight hydrocarbon chain component and R P2 At least two of the constituent components of the molecular chain other than the low molecular weight hydrocarbon chain.
[0237] Specific examples of the constituents represented by the above formula (I-1) are shown below. In addition, as a raw material compound (isocyanate compound) for introducing the constituents represented by the above formula (I-1), for example, an isocyanate compound represented by formula (M1) and its specific example, and further polymerized 4,4'-diphenylmethane isocyanate, etc., described in International Publication No. 2018 / 020827, can be cited. In addition, in the present invention, the constituents represented by formula (I-1) and the raw material compounds introduced therein are not limited to the following specific examples and the contents recorded in the above-mentioned documents.
[0238] [Chemical formula 6]
[0239]
[0240] The raw material compound (carboxylic acid or its acid chloride, etc.) for introducing the constituent component represented by the above formula (I-2) is not particularly limited, and examples thereof include carboxylic acid or acid chloride compounds described in paragraph
[0074] of International Publication No. 2018 / 020827 and specific examples thereof.
[0241] Specific examples of the constituents represented by the above formula (I-3) or (I-4) are shown below. In addition, there are no particular restrictions on the raw material compound (diol compound or diamine compound) for introducing the constituents represented by the above formula (I-3) or (I-4), and for example, the compounds described in International Publication No. 2018 / 020827 and their specific examples can be cited, and dihydroxyacetamide can also be cited. In addition, in the present invention, the constituents represented by formula (I-3) or (I-4) and the raw material compounds introduced therein are not limited to the following specific examples and the contents described in the above-mentioned documents.
[0242] In the specific examples described below, when a constituent component has a repeating structure, the number of repetitions is an integer greater than or equal to 1 and is appropriately set within the range satisfying the molecular weight or the number of carbon atoms of the above-mentioned molecular chain.
[0243] [Chemical formula 7]
[0244]
[0245] In formula (I-5), R P3 It represents an aromatic or aliphatic linking group (quadrivalent), and is preferably a linking group represented by any one of the following formulae (i) to (iix).
[0246] [Chemical formula 8]
[0247]
[0248] In formulas (i) to (iix), X 1 represents a single bond or a divalent linking group. As the divalent linking group, an alkylene group having 1 to 6 carbon atoms (e.g., methylene, vinyl, propenyl) is preferred. As the propenyl group, 1,3-hexafluoro-2,2-propanediyl is preferred. L represents -CH2=CH2- or -CH2-. R X and R Y In each formula, * represents a bonding site to the carbonyl group in formula (I-5). X and R YThe substituents that can be used are not particularly limited, and examples include the substituent Z described below, preferably an alkyl group (preferably having 1 to 12 carbon atoms, more preferably 1 to 6, and further preferably 1 to 3) or an aryl group (preferably having 6 to 22 carbon atoms, more preferably 6 to 14, and further preferably 6 to 10).
[0249] The carboxylic acid dianhydride represented by the above formula (I-5) and the raw material compound (diamine compound) for introducing the constituent components represented by the above formula (I-6) are not particularly limited, and examples thereof include the compounds described in International Publication No. 2018 / 020827 and International Publication No. 2015 / 046313 and specific examples thereof.
[0250] R P1 , R P2 and R P3 Each of them may have a substituent. There is no particular limitation on the substituent, and examples thereof include the substituent Z described below, and preferably R M2 The above-mentioned substituents which can be used.
[0251] The polyurethane is as follows: in addition to the constituent component represented by the formula (I-1), as a constituent component represented by the above formula (I-3) or formula (I-4), preferably by formula (I-3), preferably having R P2 A component (preferably a component represented by the following formula (I-3A)) comprising a chain of low molecular weight hydrocarbon groups (as a functional group, preferably a group having an ether group or a carbonyl group or both, more preferably a group having a carboxyl group) and R P2 As a molecular chain, a constituent component of the above hydrocarbon polymer chain (preferably a constituent component represented by the following formula (I-3C)), R P2 The molecular chain is at least one of the constituent components of the above-mentioned polyalkylene oxide chain (preferably a constituent component represented by the following formula (I-3B)).
[0252] [Chemical formula 9]
[0253]
[0254] In formula (I-1), R P1 As described above. In formula (I-3A), R P2A represents a chain composed of a low molecular weight hydrocarbon group (preferably an aliphatic hydrocarbon group), and as a functional group, preferably has at least one group selected from the functional group group (Ia) described below, more preferably has a group containing an ether group or a carbonyl group or both, and further preferably has a carboxyl group. For example, bis(hydroxymethyl)acetic acid compounds such as 2,2-bis(hydroxymethyl)butyric acid can be cited. In formula (I-3B), R P2B represents a polyalkyleneoxy chain. In formula (I-3C), R P2CRepresents a hydrocarbon polymer chain. P2A The chain composed of low molecular weight hydrocarbon groups can be R P2B The polyalkylene oxide chain and the polyalkylene oxide chain may be R P2C The meanings of the hydrocarbon polymer chains are respectively the same as those in the above formula (I-3) which can be represented by R P2 The aliphatic hydrocarbon group, polyalkyleneoxy chain and hydrocarbon polymer chain have the same meanings and are preferably the same.
[0255] In addition, the content of the structural components represented by the above-mentioned each formula in the polyurethane will be described later.
[0256] The polyurethane preferably has a constituent component containing a polyether structure in the main chain. Among them, it is preferred to have at least two types of polyether structures in the main chain.
[0257] In the present invention, the "polyether structure" refers to a structure in which two or more alkyleneoxy groups are connected (also referred to as a polyalkyleneoxy chain or an alkylene oxide chain), for example, a -(O-alkylene)n- structure (n represents the degree of polymerization and is a number greater than or equal to 2).
[0258] The "polyether structure" may be a single polyalkyleneoxy chain or a structure derived from a copolymer of at least two polyalkyleneoxy chains (having different chemical structures). In the present invention, a single polyalkyleneoxy chain is preferred.
[0259] The "polyether structure" is incorporated into the main chain of the polymer via an atom or a linking group as appropriate. The atom and the linking group in this case have the same meanings as those listed in X in the formula (I-7) described later.
[0260] The constituent component including a polyether structure is not particularly limited, and examples thereof include constituent components derived from polyether polyols such as polyalkylene glycols and constituent components derived from polyether polyamines.
[0261] In the present invention, "at least two types" of polyether structures refers to the differences and similarities of the constituents forming the main chain and the positions of incorporation into the main chain. The number of types of polyether structures having (alkylene) chemical structures different from each other is at least 2, and the number of types of polyether structures having the same chemical structure is 1 regardless of whether they are incorporated into different constituents or a plurality of them are incorporated into one constituent.
[0262] The number of types of the polyether structures possessed by the polyurethane may be 2 or more, preferably 2 or 3, and more preferably 2.
[0263] The alkylene oxide group forming the polyether structure is not particularly limited, and examples thereof include the alkylene oxide group which can be used as the above R P2 In the polyalkylene oxide chain used, the number of carbon atoms of the alkylene group in the alkyleneoxy group is preferably 1 to 6, more preferably 2 to 4.
[0264] The combination of polyether structures is not particularly limited, but is preferably at least two polyether structures selected from polyethyleneoxy chains, polypropyleneoxy chains, and polytetramethyleneoxy chains. A combination comprising polyethyleneoxy chains, polypropyleneoxy chains, or polytetramethyleneoxy chains is more preferred, and a combination comprising polyethyleneoxy chains and polypropyleneoxy chains is further preferred.
[0265] The (number average) molecular weight of at least two polyether structures is not particularly limited, but is preferably 400 or less, more preferably 350 or less, further preferably 300 or less, and particularly preferably 250 or less. The lower limit of the (number average) molecular weight is not particularly limited, but is preferably 100 or more, more preferably 150 or more.
[0266] In the present invention, the (number average) molecular weight of at least two polyether structures refers to the sum of the products of the (number average) molecular weight and the molar fraction of each polyether structure.
[0267] The (number average) molecular weight of each polyether structure is a value measured by the method described below on a compound (usually, a compound having hydrogen atoms bonded to each end, such as a polyether polyol described below) into which a constituent component containing a polyether structure (not incorporated in the main chain) is introduced.
[0268] The (number average) molecular weight of each polyether structure is not particularly limited, and is appropriately set within the range satisfying the above-mentioned "number average molecular weight of at least two polyether structures".
[0269] Furthermore, the degree of polymerization of each polyether structure is not particularly limited as long as it is 2 or more, and is appropriately set within the range satisfying the above-mentioned "number average molecular weight of at least two polyether structures". The degree of polymerization also depends on the number of carbon atoms of the alkyleneoxy group, and is, for example, preferably 2 to 10, more preferably 3 to 8, and even more preferably 2 to 5.
[0270] As a structural component containing a polyether structure, the structural component represented by following formula (I-7) is mentioned, for example.
[0271] [Chemical formula 10]
[0272]
[0273] In the formula, X represents a single bond, an oxygen atom or a nitrogen atom or a group containing a linking group, and R P4A and R P4B n1 and n2 represent different alkylene groups.
[0274] X can be appropriately selected according to the terminal group of the alkyleneoxy chain in the above formula. For example, when the terminal of the alkyleneoxy group is an oxygen atom, it becomes a single bond or a group containing a linking group, and when the terminal of the alkyleneoxy group is an alkylene group, it becomes an oxygen atom or a nitrogen atom or a group containing a linking group. As a group containing a linking group that can be used as X, a group consisting of a linking group, a group combining a linking group and an oxygen atom or a nitrogen atom can be cited. As the linking group, there is no particular limitation, for example, a group obtained by further removing one hydrogen atom from each group listed in the substituent Z can be cited, and preferably a group that can be used as R can be cited. P4A or R P4B The two X's in the constituent represented by the above formula (I-7) may be the same or different.
[0275] Can be used as R P4A and R P4B The alkylene group used is not particularly limited and has the same meaning as the alkylene group in the alkyleneoxy group forming the polyether structure, and the preferred alkylene group is also the same. P4A and R P4B The combinations of are the same as those explained in the combination of the above-mentioned polyether structures, and the preferred combinations are also the same.
[0276] n1 and n2 each represent a degree of polymerization, n1 is a number greater than or equal to 2, and n2 is a number greater than 0 or 1, and may be a number greater than or equal to 2.
[0277] When n2 is 0, the constituent represented by formula (I-7) becomes a constituent comprising a separate polyalkylene oxide chain. In this form, the main chain of the polyurethane has at least 2 different constituents represented by the above formula (I-7), preferably 2 or 3, more preferably 2. In this form, the constituent represented by formula (I-7) is preferably derived from at least 2 constituents selected from polyethylene glycol, polypropylene glycol and polytetramethylene ether glycol. In addition, it is also possible to have a constituent represented by formula (I-7) with n2 being a number greater than 1.
[0278] In this embodiment, the (number average) molecular weight of the two or more different constituents represented by formula (I-7) and the (number average) molecular weight of each constituent have the same meaning as the (number average) molecular weight of the at least two polyether structures, and the preferred range is also the same. In addition, n1 in the two or more different constituents represented by formula (I-7) is appropriately set within the range satisfying the (number average) molecular weight, has the same meaning as the degree of polymerization of the polyether structure, and the preferred range is also the same.
[0279] When n2 is a number greater than 1, the constituent represented by formula (I-7) becomes a constituent of a copolymer comprising two polyalkyleneoxy chains. The bonding mode of the two polyalkyleneoxy chains in the copolymer is not particularly limited, and may be a random bond, a block bond, or an alternating bond. In this form, the main chain of the polyurethane may have at least one constituent represented by the above formula (I-7), preferably one. In this form, as a constituent represented by formula (I-7), for example, a constituent composed of a copolymer of a polyethyleneoxy chain and a polypropyleneoxy chain may be cited.
[0280] The (number average) molecular weight of the constituent represented by formula (I-7) has the same meaning as the (number average) molecular weight of the above-mentioned at least two polyether structures, and the preferred range is also the same. In addition, the (number average) molecular weights of the two polyalkyleneoxy chains have the same meaning as the (number average) molecular weights of the above-mentioned polyether structures, and the preferred ranges are also the same. When there are multiple identical polyalkyleneoxy chains, the (number average) molecular weight of the polyalkyleneoxy chains is the total molecular weight. In addition, n1 and n2 are appropriately set within the range that satisfies the (number average) molecular weight, and have the same meaning as the degree of polymerization of the above-mentioned polyether structure, and the preferred range is also the same.
[0281] The above formula (I-7) specifies a constituent containing two polyether structures (alkyleneoxy chains). However, in the present invention, the constituent containing a polyether structure, the constituent represented by the above formula (I-7) may contain three or more polyether structures.
[0282] Specific examples of the constituent components represented by the above formula (I-7) are shown below, but the present invention is not limited thereto. In the following specific examples, the degree of polymerization of the alkyleneoxy group is omitted, but is set within the above range.
[0283] [Chemical formula 11]
[0284]
[0285] The polyurethane may have components other than the components represented by the above formulae. Such components are not particularly limited as long as they can be polymerized sequentially with the raw material compounds into which the components represented by the above formulae are introduced.
[0286] The (total) content of the constituent components represented by the above-mentioned formulas (I-1) to (I-7) in the polyurethane is not particularly limited, but is preferably 5 to 100% by mass, more preferably 10 to 100% by mass, further preferably 50 to 100% by mass, and further preferably 80 to 100% by mass. The upper limit of the content can be set to 90% by mass or less, for example, regardless of the above-mentioned 100% by mass.
[0287] The content of components other than the components represented by the above formulae in the polyurethane is not particularly limited, but is preferably 50% by mass or less.
[0288] When the polyurethane has a constituent component represented by any one of the above formulas (I-1) to (I-6), the content thereof is not particularly limited and can be set to the following ranges.
[0289] That is, the content of the constituent represented by formula (I-1) or formula (I-2) or the constituent derived from carboxylic dianhydride represented by formula (I-5) in the polyurethane is not particularly limited, but is preferably 10 to 50 mol %, more preferably 20 to 50 mol %, and further preferably 30 to 50 mol %.
[0290] The content of the constituent represented by formula (I-3), formula (I-4) or formula (I-6) in the polyurethane is not particularly limited, but is preferably 0 to 50 mol %, more preferably 5 to 40 mol %, and further preferably 10 to 30 mol %.
[0291] In the constituents represented by formula (I-3) or formula (I-4), R P2 The content of the constituent component of a chain composed of a low molecular weight hydrocarbon group (for example, the constituent component represented by the above formula (I-3A)) in the polyurethane is not particularly limited, and is, for example, preferably 0 to 50 mol%, more preferably 1 to 30 mol%, further preferably 2 to 20 mol%, and further preferably 4 to 10 mol%.
[0292] In the constituent represented by formula (I-3) or formula (I-4), R P2 The content of the polyalkylene oxide chain as a molecular chain constituent (e.g., a constituent represented by the above formula (I-3B)) in the polyurethane is not particularly limited, and is, for example, preferably 0 to 50 mol%, more preferably 0 to 45 mol%, and further preferably 0 to 43 mol%.
[0293] In the constituents represented by formula (I-3) or formula (I-4), R P2 The content in the polyurethane of the constituent component whose molecular chain is the above-mentioned hydrocarbon polymer chain (for example, the constituent component represented by the above-mentioned formula (I-3C)) is not particularly limited, and is, for example, preferably 0 to 50 mol%, more preferably 1 to 45 mol%, further preferably 3 to 40 mol%, further preferably 3 to 30 mol%, particularly preferably 3 to 20 mol%, and most preferably 3 to 10 mol%.
[0294] The (total) content of the constituent having a polyether structure, such as the constituent represented by formula (I-7), in the polyurethane is not particularly limited, and is, for example, preferably 10 to 60 mol%, more preferably 20 to 55 mol%, further preferably 30 to 50 mol%, and particularly preferably 35 to 45 mol%.
[0295] When the polyurethane has a plurality of different constituents represented by formula (I-7), the content of each constituent is appropriately determined within the range satisfying the above (total) content. For example, when there are two different constituents represented by formula (I-7), the content of one constituent (preferably a constituent having a polyether structure formed by an alkylene oxide with a large molecular weight) is preferably 5 to 30 mol%, more preferably 10 to 25 mol%, and further preferably 15 to 20 mol%. The content of another constituent (preferably a constituent having a polyether structure formed by an alkylene oxide with a small molecular weight) is preferably 10 to 50 mol%, more preferably 15 to 40 mol%, and further preferably 20 to 30 mol%. In addition, the content ratio of one constituent to another constituent [one constituent: another constituent] is not particularly limited, for example, preferably 10:90 to 80:20, more preferably 20:80 to 70:30.
[0296] On the other hand, when the polyurethane has three or more different constituents represented by formula (I-7), the constituent having a polyether structure formed by an alkylene oxide with the smallest molecular weight is set as the above-mentioned other constituent, and the other constituents are set as the above-mentioned one constituent.
[0297] In addition, when the constituent represented by formula (I-7) also corresponds to the constituent represented by formula (I-3B), the content of the constituent represented by formula (I-7) is independent of the above-mentioned content of the constituent represented by formula (I-3B), and is set to the above-mentioned content described in the constituent represented by the above-mentioned formula (I-7).
[0298] In addition, when polyurethane has a plurality of constituent components represented by various formulae, the above content of each constituent component is set as the total content.
[0299] -Functional Groups-
[0300] The polyurethane preferably has a functional group for improving the wettability or adsorption of the surface of solid particles such as inorganic solid electrolytes. As such functional groups, groups showing physical interactions such as hydrogen bonds on the surface of solid particles and groups that can form chemical bonds with groups present on the surface of solid particles can be cited, specifically, more preferably having at least one group selected from the following functional group group (Ia). Among them, from the viewpoint of more effectively showing wettability or adsorption on the surface of solid particles, it is preferred not to have more than two groups that can form bonds between functional groups.
[0301] <Functional group (Ia)>
[0302] Carboxyl, sulfonic acid (-SO3H), phosphoric acid (-PO4H2), amino (-NH2), hydroxyl, sulfanyl, isocyanate, alkoxysilyl, and groups with fused ring structures of three or more rings
[0303] The group capable of forming a salt, such as a carboxyl group, a sulfonic acid group, a phosphoric acid group, a hydroxyl group, a thiamine group, etc., may be a salt thereof, for example, a sodium salt and a calcium salt thereof.
[0304] The alkoxysilyl group may be a silyl group in which the Si atom is substituted with at least one alkoxy group (preferably having 1 to 12 carbon atoms), and other substituents on the Si atom include alkyl groups and aryl groups. As the alkoxysilyl group, for example, the alkoxysilyl group described in the substituent Z described later can be preferably applied.
[0305] The group having a fused ring structure of three or more rings is preferably a group having a cholesterol ring structure or a group having a structure in which three or more aromatic rings are fused, and is more preferably a cholesterol residue or a pyrene group.
[0306] Carboxyl, sulfonic acid (-SO3H), phosphoric acid (-PO4H2), hydroxyl and alkoxysilyl groups have high adsorption to inorganic solid electrolytes or positive electrode active materials, and groups with fused ring structures of more than three rings have high adsorption to negative electrode active materials. Amino (-NH2), sulfanyl and isocyanate groups have high adsorption to inorganic solid electrolytes.
[0307] The polyurethane may have a functional group selected from the functional group group (Ia) in any constituent component forming the polymer, and may have it on any of the main chain or side chain of the polymer. As a constituent component having the above functional group, for example, a constituent component represented by formula (I-3A) can be cited.
[0308] The content of the functional group selected from the functional group group (Ia) in the polyurethane is not particularly limited. For example, the proportion of the constituent having the functional group selected from the above-mentioned functional group group (Ia) in all the constituents constituting the polyurethane is preferably 0.01 to 50 mol%, preferably 0.02 to 49 mol%, more preferably 0.1 to 40 mol%, further preferably 1 to 30 mol%, and particularly preferably 3 to 25 mol%.
[0309] The polyurethane (each component and raw material compound) may have a substituent. The substituent is not particularly limited, but preferably, a group selected from the following substituent Z is mentioned.
[0310] Polyurethane can be synthesized by selecting a raw material compound according to the type of bond possessed by the main chain by a known method, and by subjecting the raw material compound to polyaddition or polycondensation, etc. As a synthesis method, for example, International Publication No. 2018 / 151118 can be referred to.
[0311] Examples of the preferred polyurethane include groups in which two types of polyether structures are incorporated into the main chain of each polyurethane described in International Publication Nos. 2018 / 020827 and 2015 / 046313, and Japanese Patent Application Laid-Open No. 2015-088480.
[0312] (Physical properties or characteristics of polymer binder or fluorine-based copolymer forming polymer binder, etc.)
[0313] The water concentration of the polymer binder is preferably 100 ppm (mass basis) or less. The polymer binder may be obtained by crystallizing the fluorine-based copolymer and then drying it, or the polymer binder dispersion may be used directly.
[0314] The fluorine-based copolymer is preferably amorphous. In the present invention, the polymer being "amorphous" typically means that no endothermic peak due to crystal melting is observed when measured at the glass transition temperature.
[0315] The shape of the polymer binder is not particularly limited, and may be in the form of particles. The particle shape at this time may be flat, amorphous, etc., but is preferably spherical or granular. The particle size of the particulate polymer binder is not particularly limited, but is preferably 0.1 nm or more, more preferably 1 nm or more, further preferably 5 nm or more, particularly preferably 10 nm or more, and most preferably 50 nm or more. As an upper limit, it is preferably 1.0 μm or less, further preferably 700 nm or less, and particularly preferably 500 nm or less.
[0316] The average particle size of the composite polymer particles can be measured in the same manner as the average particle size of the inorganic solid electrolyte described above.
[0317] In addition, the average particle size of the polymer binder in the constituent layer of the all-solid-state secondary battery can be measured, for example, by disassembling the battery and peeling off the constituent layer containing the polymer binder, measuring the constituent layer and removing the measured value of the particle size of particles other than the polymer binder that has been measured in advance.
[0318] The mass average molecular weight of the polymer is not particularly limited, and is, for example, preferably 5,000 or more, more preferably 10,000 or more, further preferably 20,000 or more, and particularly preferably 50,000 or more. The upper limit is, in practice, 5,000,000 or less, preferably 3,000,000 or less, more preferably 1,000,000 or less, and particularly preferably 500,000 or less.
[0319] - Determination of Molecular Weight -
[0320] In the present invention, the molecular weight of a polymer or a polymer chain, unless otherwise specified, refers to the mass average molecular weight or number average molecular weight calculated by standard polystyrene obtained by gel permeation chromatography (GPC). As a method for determining the molecular weight, a method basically set to the following condition 1 or condition 2 (preferred) can be cited. Among them, a suitable eluent can be appropriately selected and used according to the type of the polymer.
[0321] (Condition 1)
[0322] Column: Two TOSOH TSKgel Super AWM-H (trade name, manufactured by TOSOH CORPORATION) connected
[0323] Carrier: 10mMLiBr / N-methylpyrrolidone
[0324] Measurement temperature: 40℃
[0325] Carrier flow rate: 1.0ml / min
[0326] Sample concentration: 0.1 mass%
[0327] Detector: RI (refractive index) detector
[0328] (Condition 2)
[0329] Column: A column connected with TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000, or TOSOH TSKgel Super HZ2000 (all trade names, manufactured by Tosoh Corporation) was used.
[0330] Carrier: Tetrahydrofuran
[0331] Measurement temperature: 40℃
[0332] Carrier flow rate: 1.0ml / min
[0333] Sample concentration: 0.1 mass%
[0334] Detector: RI (refractive index) detector
[0335] The polymer forming the polymer binder may be a non-crosslinked polymer or a crosslinked polymer. Furthermore, when the polymer is crosslinked by heating or applying a voltage, the molecular weight may be greater than the above molecular weight. Preferably, when the all-solid-state secondary battery is first used, the mass average molecular weight of the polymer is within the above range.
[0336] The inorganic solid electrolyte-containing composition of the present invention may contain one polymer binder or may contain a plurality of polymer binders.
[0337] The content of the polymer binder in the composition containing the inorganic solid electrolyte is not particularly limited, but from the viewpoint of adhesion and resistance, it is preferably 0.1 to 10.0 mass %, more preferably 0.2 to 5.0 mass %, and further preferably 0.3 to 4.0 mass %, based on 100 mass % of the solid content.
[0338] In the present invention, the mass ratio of the total mass (total amount) of the inorganic solid electrolyte and the active material to the mass of the binder [(mass of the inorganic solid electrolyte + mass of the active material) / (total mass of the binder)] is preferably in the range of 1,000 to 1. In addition, the ratio is more preferably 500 to 2, and further preferably 100 to 10.
[0339] <Dispersion medium>
[0340] The inorganic solid electrolyte-containing composition of the present invention may be a solid mixture not containing a dispersion medium for dispersing the above-mentioned components, but preferably contains a dispersion medium, and is preferably a slurry in which solid particles such as an inorganic solid electrolyte are dispersed in a dispersion medium.
[0341] The dispersion medium may be any organic compound that is liquid in the use environment, and examples thereof include various organic solvents, specifically, alcohol compounds, ether compounds, amide compounds, amine compounds, ketone compounds, aromatic compounds, aliphatic compounds, nitrile compounds, ester compounds, and the like.
[0342] The dispersion medium may be a non-polar dispersion medium (hydrophobic dispersion medium) or a polar dispersion medium (hydrophilic dispersion medium), and a non-polar dispersion medium is preferred from the viewpoint of being able to exhibit excellent dispersibility. A non-polar dispersion medium generally refers to a property of having low affinity for water, but in the present invention, for example, ester compounds, ketone compounds, ether compounds, aromatic compounds, aliphatic compounds, etc. may be cited.
[0343] Examples of the alcohol compound include methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, ethylene glycol, propylene glycol, glycerol, 1,6-hexanediol, cyclohexanediol, sorbitol, xylitol, 2-methyl-2,4-pentanediol, 1,3-butanediol, and 1,4-butanediol.
[0344] Examples of the ether compound include alkylene glycols (diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, etc.), alkylene glycol monoalkyl ethers (ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, etc.), alkylene glycol dialkyl ethers (ethylene glycol dimethyl, etc.), dialkyl ethers (dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, etc.), and cyclic ethers (tetrahydrofuran, dioxane (including 1,2-, 1,3-, and 1,4-isomers), etc.).
[0345] Examples of the amide compound include N,N-dimethylformamide, N-methyl-2-pyrrolidone, 2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, ε-caprolactam, formamide, N-methylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropaneamide, and hexamethylphosphoric triamide.
[0346] Examples of the amine compound include triethylamine, diisopropylethylamine, and tri-n-butylamine.
[0347] Examples of the ketone compound include acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclopentanone, cyclohexanone, cycloheptanone, dipropyl ketone, dibutyl ketone, diisopropyl ketone, diisobutyl ketone (DIBK), isobutyl propyl ketone, sec-butyl propyl ketone, amyl propyl ketone, and butyl propyl ketone.
[0348] Examples of the aromatic compound include benzene, toluene, and xylene.
[0349] Examples of the aliphatic compound include hexane, heptane, octane, nonane, decane, dodecane, cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, cyclooctane, decalin, paraffin, gasoline, naphtha, kerosene, and light oil.
[0350] Examples of the nitrile compound include acetonitrile, propionitrile, and isobutyronitrile.
[0351] Examples of the ester compound include ethyl acetate, butyl acetate, propyl acetate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, butyl valerate, ethyl isobutyrate, propyl isobutyrate, isopropyl isobutyrate, isobutyl isobutyrate, propyl pivalate, isopropyl pivalate, butyl pivalate, and isobutyl pivalate.
[0352] In the present invention, among these, ether compounds, ketone compounds, aromatic compounds, aliphatic compounds, and ester compounds are preferred, and ketone compounds, aliphatic compounds, and ester compounds are more preferred.
[0353] The number of carbon atoms in the compound constituting the dispersion medium is not particularly limited, but is preferably 2 to 30, more preferably 4 to 20, further preferably 6 to 15, and particularly preferably 7 to 12.
[0354] The boiling point of the dispersion medium at normal pressure (1 atmosphere) is preferably 50° C. or higher, more preferably 70° C. or higher. The upper limit is preferably 250° C. or lower, more preferably 220° C. or lower.
[0355] When the composition containing an inorganic solid electrolyte of the present invention contains a dispersion medium, the dispersion medium can be at least one, or more than two. In addition, the content of the dispersion medium is not particularly limited and can be appropriately set. For example, in a composition containing an inorganic solid electrolyte, it is preferably 20 to 80% by mass, more preferably 30 to 70% by mass, and particularly preferably 40 to 60% by mass.
[0356] <Active substances>
[0357] The composition containing the inorganic solid electrolyte of the present invention may further contain an active material capable of inserting and extracting ions of metals belonging to Group 1 or Group 2 of the periodic table. As the active material, as described below, positive electrode active materials and negative electrode active materials can be cited.
[0358] In the present invention, a composition containing an inorganic solid electrolyte and containing an active material (positive electrode active material or negative electrode active material) may be referred to as an electrode composition (positive electrode composition or negative electrode composition).
[0359] (Positive electrode active material)
[0360] The positive electrode active material is an active material that can embed and deintercalate ions of metals belonging to Group 1 or Group 2 of the periodic table, preferably an active material that can reversibly embed and deintercalate lithium ions. As long as the material is a material having the above-mentioned characteristics, there is no particular limitation, and it can be a transition metal oxide or organic matter, sulfur, or other element that can be composited with Li that decomposes the battery.
[0361] Among them, as the positive electrode active material, a transition metal oxide is preferably used, and a transition metal oxide having a transition metal element Ma (one or more elements selected from Co, Ni, Fe, Mn, Cu and V) is more preferably used. In addition, the element Mb (elements of the 1st (Ia) group of the metal periodic table other than lithium, elements of the 2nd (IIa) group, Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P and B, etc.) can also be mixed in the transition metal oxide. As a mixed amount, it is preferably 0 to 30 mol% relative to the amount of the transition metal element Ma (100 mol%). It is more preferably mixed and synthesized in a manner such that the molar ratio of Li / Ma becomes 0.3 to 2.2.
[0362] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.
[0363] Specific examples of transition metal oxides having a layered rock salt structure (MA) include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).
[0364] Specific examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8 and Li2NiMn3O8.
[0365] As (MC) lithium-containing transition metal phosphate compounds, for example, olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate) can be listed.
[0366] Examples of the (MD) lithium-containing transition metal halophosphate compound include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.
[0367] Examples of the (ME) lithium-containing transition metal silicate compound include Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.
[0368] In the present invention, (MA) is preferably a transition metal oxide having a layered rock salt structure, and more preferably LCO or NMC.
[0369] The shape of the positive electrode active material is not particularly limited, and is preferably in the form of particles. The particle size (volume average particle size) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1 to 50 μm. The particle size of the positive electrode active material particles can be measured in the same manner as the particle size of the above-mentioned inorganic solid electrolyte. In order to make the positive electrode active material a specified particle size, a conventional pulverizer or classifier is used. For example, a mortar, a ball mill, a sand mill, a vibrating ball mill, a satellite ball mill, a planetary ball mill, and a rotary airflow type jet mill or a sieve can be appropriately used. During pulverization, wet pulverization in which a dispersion medium such as water or methanol coexists can also be appropriately performed. In order to set the desired particle size, it is preferably classified. The classification is not particularly limited, and can be performed using a sieve, a wind classifier, etc. Both dry and wet classification can be used.
[0370] The positive electrode active material obtained by the calcination method may be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.
[0371] The positive electrode active material may be used alone or in combination of two or more.
[0372] When a positive electrode active material layer is formed, the positive electrode active material layer has a unit area (cm 2 The mass (mg) (weight per unit area) of the positive electrode active material is not particularly limited. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm 2 .
[0373] The content of the positive electrode active material in the composition containing the inorganic solid electrolyte is not particularly limited, and is preferably 10 to 97% by mass, more preferably 30 to 95% by mass, further preferably 40 to 93% by mass, and particularly preferably 50 to 90% by mass, based on 100% by mass of the solid content.
[0374] (Negative electrode active material)
[0375] The negative electrode active material is an active material that can embed and deintercalate ions of metals belonging to Group 1 or Group 2 of the periodic table, preferably an active material that can reversibly embed and deintercalate lithium ions. The material is not particularly limited as long as it is a material having the above-mentioned characteristics, and carbonaceous materials, metal oxides, metal composite oxides, lithium monomers, lithium alloys, negative electrode active materials that can form alloys with lithium (can be alloyed), etc. can be cited. Among them, from the viewpoint of reliability, carbonaceous materials, metal composite oxides or lithium monomers are preferably used. From the viewpoint of being able to increase the capacity of an all-solid-state secondary battery, an active material that can be alloyed with lithium is preferably used. The solid particles in the constituent layer formed by the solid electrolyte composition of the present invention are firmly bonded to each other, so a negative electrode active material that can form an alloy with lithium can be used as a negative electrode active material. Thus, the capacity of the all-solid-state secondary battery can be increased and the life of the battery can be extended.
[0376] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon. For example, carbon black such as petroleum pitch, acetylene black (AB), graphite (natural graphite, artificial graphite such as vapor-grown graphite, etc.), and various synthetic resins such as PAN (polyacrylonitrile) resin or furfuryl alcohol resin can be calcined to form the carbonaceous material. In addition, various carbon fiber types such as PAN-based carbon fiber, cellulose-based carbon fiber, asphalt-based carbon fiber, vapor-grown carbon fiber, dehydrated PVA (polyvinyl alcohol)-based carbon fiber, lignin carbon fiber, glassy carbon fiber and activated carbon fiber, mesophase microspheres, graphite whiskers and flat graphite can also be listed.
[0377] These carbonaceous materials are divided into difficult graphitization carbonaceous materials (also referred to as hard carbon) and graphite-based carbonaceous materials by the degree of graphitization. In addition, the carbonaceous material preferably has the surface spacing or density and crystallite size recorded in Japanese Patent Publication No. 62-22066, Japanese Patent Publication No. 2-6856, and Japanese Patent Publication No. 3-45473. Carbonaceous materials do not need to be a single material, and a mixture of natural graphite and artificial graphite recorded in Japanese Patent Publication No. 5-90844, and graphite with a coating layer recorded in Japanese Patent Publication No. 6-4516 can also be used.
[0378] As the carbonaceous material, hard carbon or graphite is preferably used, and graphite is more preferably used.
[0379] As oxides of metal or semi-metal elements suitable as negative electrode active materials, there are no particular restrictions as long as they are oxides that can absorb and release lithium, and examples include oxides of metal elements (metal oxides), composite oxides of metal elements or composite oxides of metal elements and semi-metal elements (collectively referred to as metal composite oxides), and oxides of semi-metal elements (semi-metal oxides). As these oxides, amorphous oxides are preferred, and further preferred examples are chalcogenides, which are reaction products of metal elements and elements of Group 16 of the periodic table. In the present invention, semi-metal elements refer to elements that show properties intermediate between metal elements and non-semi-metal elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and further include three elements of selenium, polonium and astatine. In addition, amorphous refers to a material having a broad scattering band with a vertex in the region of 20° to 40° at a 2θ value by an X-ray diffraction method using CuKα rays, and may also have crystalline diffraction lines. The strongest intensity among the crystalline diffraction lines appearing in the region of 40° to 70° at 2θ values is preferably 100 times or less, more preferably 5 times or less, the intensity of the diffraction line at the top of the broad scattering band appearing in the region of 20° to 40° at 2θ values, and particularly preferably a diffraction line without crystallinity.
[0380] Among the compound groups including the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and (complex) oxides or chalcogenides containing one or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (e.g., Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi) are particularly preferred. Specific examples of preferred amorphous oxides and chalcogenides include, for example, Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3, or Sb2S5.
[0381] Preferred negative electrode active materials that can be used together with the amorphous oxides containing Sn, Si, or Ge as the core include carbonaceous materials that can absorb and / or release lithium ions or lithium metal, lithium monomers, lithium alloys, and negative electrode active materials that can alloy with lithium.
[0382] From the viewpoint of high current density charge and discharge characteristics, the oxide of metal or semimetal element, especially metal (composite) oxide and the above-mentioned chalcogenide preferably contains at least one of titanium and lithium as a constituent component. As the metal composite oxide containing lithium (lithium composite metal oxide), for example, a composite oxide of lithium oxide and the above-mentioned metal (composite) oxide or the above-mentioned chalcogenide can be cited, and more specifically, Li2SnO2 can be cited.
[0383] The negative electrode active material, such as a metal oxide, preferably contains titanium (titanium oxide). Specifically, due to Li4Ti5O 12 (Lithium titanate [LTO]) has a small volume change when absorbing and releasing lithium ions, and therefore has excellent rapid charge and discharge characteristics, and is preferred in terms of being able to suppress electrode degradation and extend the life of lithium ion secondary batteries.
[0384] The lithium alloy as the negative electrode active material is not particularly limited as long as it is an alloy generally used as a negative electrode active material for secondary batteries, and examples thereof include lithium aluminum alloys.
[0385] The negative electrode active material that can form an alloy with lithium is not particularly limited as long as it is a negative electrode active material commonly used as a secondary battery. This active material has a large expansion and contraction caused by the charge and discharge of the all-solid-state secondary battery, and accelerates the decline in cycle characteristics, but the composition containing an inorganic solid electrolyte of the present invention contains the above-mentioned compound (SA), so it is possible to suppress the decline in cycle characteristics. As such an active material, there can be cited (negative electrode) active materials (alloys, etc.) having silicon or tin elements, metals such as Al and In, preferably a negative electrode active material (active material containing silicon element) having silicon element that can achieve a higher battery capacity, more preferably an active material containing silicon element having a silicon element content of more than 50 mol% of all constituent elements.
[0386] Generally, the negative electrode containing these negative electrode active materials (for example, Si negative electrode containing active materials containing silicon elements, Sn negative electrode containing active materials having tin elements, etc.) can absorb more Li ions compared with carbon negative electrodes (graphite and acetylene black, etc.). That is, the amount of Li ions absorbed per unit mass increases. Therefore, the battery capacity (energy density) can be increased. As a result, it has the advantage of being able to extend the battery driving time.
[0387] As active materials containing silicon elements, for example, silicon materials such as Si and SiOx (0<x≤1), and silicon-containing alloys (for example, LaSi2, VSi2, La-Si, Gd-Si, Ni-Si) or organized active materials (for example, LaSi2 / Si) containing titanium, vanadium, chromium, manganese, nickel, copper, lanthanum, etc., and active materials containing silicon elements such as SnSiO3 and SnSiS3 and tin elements, etc. In addition, SiOx itself can be used as a negative electrode active material (semi-metallic oxide), and Si is generated by the operation of an all-solid-state secondary battery, so it can be used as a negative electrode active material (its precursor material) that can be alloyed with lithium.
[0388] Examples of negative electrode active materials containing tin include active materials containing Sn, SnO, SnO2, SnS, SnS2, and the above-mentioned silicon and tin elements, etc. Also, composite oxides with lithium oxide, such as Li2SnO2, can be cited.
[0389] In the present invention, the above-mentioned negative electrode active material can be used without particular restrictions, but from the viewpoint of battery capacity, as the negative electrode active material, it is preferably a negative electrode active material that can alloy with lithium, among which the above-mentioned silicon material or silicon-containing alloy (alloy containing silicon element) is more preferred, and it is further preferred to contain silicon (Si) or a silicon-containing alloy.
[0390] As a measurement method, inductively coupled plasma (ICP) emission spectrometry can be used. As a simple method, the chemical formula of the compound obtained by the above-mentioned calcination method can be calculated from the mass difference of the powder before and after calcination.
[0391] The shape of the negative electrode active material is not particularly limited, and is preferably in the form of particles. The volume average particle size of the negative electrode active material is not particularly limited, and is preferably 0.1 to 60 μm. The volume average particle size of the negative electrode active material particles can be measured in the same manner as the average particle size of the inorganic solid electrolyte. In order to set the particle size to a predetermined size, a conventional pulverizer or classifier is used in the same manner as the positive electrode active material.
[0392] The above-mentioned negative electrode active materials may be used alone or in combination of two or more.
[0393] When forming a negative electrode active material layer, the negative electrode active material layer has a unit area (cm 2 The mass (mg) (weight per unit area) of the negative electrode active material is not particularly limited. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm 2 .
[0394] The content of the negative electrode active material in the composition containing the inorganic solid electrolyte is not particularly limited, but is preferably 10 to 90% by mass, more preferably 20 to 85% by mass, more preferably 30 to 80% by mass, and further preferably 40 to 75% by mass based on 100% by mass of the solid content.
[0395] In the present invention, when the negative electrode active material layer is formed by charging the secondary battery, ions of metals belonging to Group 1 or Group 2 of the periodic table generated in the all-solid-state secondary battery can be used instead of the above-mentioned negative electrode active material. The negative electrode active material layer can be formed by bonding the ions with electrons to precipitate as metal.
[0396] (Encapsulation of active substances)
[0397] The surfaces of the positive electrode active material and the negative electrode active material can also be coated with different metal oxides. As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be listed. Specifically, titanate spinel, tantalum oxide, niobium oxide, lithium niobate compounds, etc. can be listed. Specifically, Li4Ti5O 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3, etc.
[0398] Furthermore, the surface of the electrode including the positive electrode active material or the negative electrode active material may be surface-treated with sulfur or phosphorus.
[0399] Furthermore, the surface of the particles of the positive electrode active material or the negative electrode active material may be subjected to a surface treatment using actinic rays or an active gas (plasma, etc.) before and after the above-mentioned surface coating.
[0400] <Conductive additive>
[0401] The inorganic solid electrolyte-containing composition of the present invention preferably contains a conductive auxiliary agent. For example, it is preferable to use a conductive auxiliary agent in combination with an active material containing silicon atoms as a negative electrode active material.
[0402] There are no particular restrictions on the conductive aid, and generally known conductive aids can be used. For example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjenblack, and furnace black, amorphous carbon such as needle coke, carbon fibers such as vapor-grown carbon fibers or carbon nanotubes, carbonaceous materials such as graphene or fullerene, and metal powders and metal fibers such as copper and nickel can be used. Conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives can also be used.
[0403] In the present invention, when an active material and a conductive aid are used in combination, among the conductive aids, when the battery is charged and discharged, the ions (preferably Li ions) of metals belonging to Group 1 or Group 2 of the periodic table are not embedded and deintercalated, and those that do not function as active materials are used as conductive aids. Therefore, among the conductive aids, those that can function as active materials in the active material layer when the battery is charged and discharged are classified as active materials rather than conductive aids. Whether or not to function as an active material when the battery is charged and discharged is determined by the combination with the active material, rather than being determined in general.
[0404] The conductive auxiliary agent may be contained alone or in combination of two or more.
[0405] The shape of the conductive auxiliary agent is not particularly limited, but is preferably in the form of particles.
[0406] When the inorganic solid electrolyte-containing composition of the present invention contains a conductive auxiliary agent, the content of the conductive auxiliary agent in the inorganic solid electrolyte-containing composition is preferably 0 to 10% by mass based on 100% by mass of the solid content.
[0407] <Lithium salt>
[0408] The inorganic solid electrolyte-containing composition of the present invention preferably further contains a lithium salt (supporting electrolyte).
[0409] The lithium salt is preferably a lithium salt generally used for such products, without particular limitation. For example, the lithium salts described in paragraphs 0082 to 0085 of JP-A-2015-088486 are preferred.
[0410] When the composition containing an inorganic solid electrolyte of the present invention contains a lithium salt, the content of the lithium salt is preferably 0.1 parts by mass or more, more preferably 5 parts by mass or more, relative to 100 parts by mass of the solid electrolyte. As an upper limit, it is preferably 50 parts by mass or less, more preferably 20 parts by mass or less.
[0411] <Dispersant>
[0412] The composition containing an inorganic solid electrolyte of the present invention can appropriately contain a dispersant. When the composition containing an inorganic solid electrolyte of the present invention contains a polymer binder, the polymer binder also acts as a dispersant, so it may not contain a dispersant other than the polymer binder, or it may contain a dispersant. As a dispersant, a dispersant commonly used in all-solid-state secondary batteries can be appropriately selected for use. Usually, the desired compound in particle adsorption, steric repulsion and / or electrostatic repulsion is appropriately used.
[0413] <Other additives>
[0414] The composition containing inorganic solid electrolyte of the present invention can appropriately contain ionic liquid, thickener, crosslinking agent (substances that undergo crosslinking reaction by free radical polymerization, polycondensation or ring-opening polymerization, etc.), polymerization initiator (substances that generate acid or free radicals by heat or light, etc.), defoamer, leveling agent, dehydrating agent, antioxidant, etc. as other ingredients other than the above-mentioned components. Ionic liquid is a liquid contained in order to further improve ionic conductivity, and known liquids can be used without particular restrictions. In addition, polymers other than the above-mentioned polymers contained in the above-mentioned adhesive, commonly used binders, etc. may be contained.
[0415] (Preparation of Composition Containing Inorganic Solid Electrolyte)
[0416] The composition containing an inorganic solid electrolyte of the present invention can be prepared as a mixture, preferably as a slurry, by mixing an inorganic solid electrolyte, the above-mentioned compound (SA), preferably a polymer binder, a dispersion medium, an active material according to the purpose, a conductive aid and an appropriate lithium salt, and any other components, for example, in various commonly used mixers.
[0417] The mixing method is not particularly limited, and the mixture may be mixed all at once or sequentially. The mixing environment is not particularly limited, and examples thereof include dry air or inert gas.
[0418] [Sheet for all-solid-state secondary batteries]
[0419] The sheet material for all-solid-state secondary batteries of the present invention is a sheet-like molded body capable of forming a constituent layer of an all-solid-state secondary battery, and includes various modes according to its use. For example, a sheet material preferably used for a solid electrolyte layer (also referred to as a solid electrolyte sheet for an all-solid-state secondary battery), a sheet material preferably used for a laminate of an electrode or an electrode and a solid electrolyte layer (electrode sheet for an all-solid-state secondary battery), etc. can be cited. In the present invention, these various sheets are collectively referred to as sheets for all-solid-state secondary batteries.
[0420] The solid electrolyte sheet for an all-solid-state secondary battery of the present invention can be a sheet having a solid electrolyte layer, and can be a sheet having a solid electrolyte layer formed on a substrate, or can be a sheet having no substrate and formed by a solid electrolyte layer. The solid electrolyte sheet for an all-solid-state secondary battery can also have other layers in addition to the solid electrolyte layer. As other layers, for example, a protective layer (peel-off sheet), a current collector, a coating, etc. can be cited.
[0421] As a solid electrolyte sheet for an all-solid-state secondary battery of the present invention, for example, a sheet having a layer composed of a composition containing an inorganic solid electrolyte of the present invention, a common solid electrolyte layer and a protective layer in sequence on a substrate can be cited. The solid electrolyte layer possessed by the solid electrolyte sheet for an all-solid-state secondary battery is preferably formed by a composition containing an inorganic solid electrolyte of the present invention. The content of each component in the solid electrolyte layer is not particularly limited, and the preferred meaning is the same as the content of each component in the solid component of the composition containing an inorganic solid electrolyte of the present invention. The thickness of each layer constituting the solid electrolyte sheet for an all-solid-state secondary battery is the same as the thickness of each layer described in the all-solid-state secondary battery described later.
[0422] As a substrate, as long as it is a substrate that can support a solid electrolyte layer, it is not particularly limited, and can include sheet bodies (plate bodies) such as materials described in the collector described later, organic materials, and inorganic materials. As organic materials, various polymers can be listed, specifically, polyethylene terephthalate, polypropylene, polyethylene, and cellulose can be listed. As inorganic materials, for example, glass and ceramics can be listed.
[0423] The electrode sheet for all-solid-state secondary batteries of the present invention (also referred to as "electrode sheet" for short) can be an electrode sheet with an active material layer, and can be a sheet in which the active material layer is formed on a substrate (collector), or can be a sheet without a substrate and formed by an active material layer. The electrode sheet is usually a sheet with a collector and an active material layer, but also includes a form having a collector, an active material layer and a solid electrolyte layer in sequence, and a form having a collector, an active material layer, a solid electrolyte layer and an active material layer in sequence. The solid electrolyte layer and active material layer possessed by the electrode sheet are preferably formed by a composition containing an inorganic solid electrolyte of the present invention. The content of each component in the solid electrolyte layer or the active material layer is not particularly limited, and the preferred meaning is the same as the content of each component in the solid component of the composition containing an inorganic solid electrolyte (electrode composition) of the present invention. The thickness of each layer constituting the electrode sheet of the present invention is the same as the thickness of each layer described in the all-solid-state secondary battery described later. The electrode sheet of the present invention may have the above-mentioned other layers.
[0424] In the sheet material for all-solid-state secondary batteries of the present invention, at least one layer of the solid electrolyte layer and the active material layer is formed by the composition containing an inorganic solid electrolyte of the present invention, and preferably the active material layer is formed by the composition containing an inorganic solid electrolyte of the present invention. Therefore, the constituent layer formed by the composition containing an inorganic solid electrolyte of the present invention can achieve a large layer density ratio as shown in the embodiments described later. By using the sheet material for all-solid-state secondary batteries of the present invention as the constituent layer of the all-solid-state secondary battery, the excellent cycle characteristics and low resistance of the all-solid-state secondary battery can be achieved. In particular, the negative electrode sheet for all-solid-state secondary batteries and the all-solid-state secondary batteries formed by the negative electrode active material of the composition containing an inorganic solid electrolyte of the present invention can show a high active material capacity and achieve low resistance and high cycle characteristics even if a negative electrode active material that can form an alloy with lithium is used as a negative electrode active material.
[0425] [Method for producing a sheet for an all-solid-state secondary battery]
[0426] The manufacturing method of the sheet material for all-solid-state secondary batteries of the present invention is not particularly limited, and the above-mentioned layers can be formed using the composition containing an inorganic solid electrolyte of the present invention. For example, when the composition containing an inorganic solid electrolyte of the present invention is a solid mixture, a method of forming by press molding on a substrate or a collector can be cited. On the other hand, when the composition containing an inorganic solid electrolyte of the present invention contains a dispersion medium, it is preferred to cite a method of forming a layer (coating drying layer) composed of a composition containing an inorganic solid electrolyte on a substrate or a collector (may be via another layer.). Film (coating drying) is preferably cited. Thus, a sheet material for all-solid-state secondary batteries having a substrate or a collector and a coating drying layer can be prepared. Here, the coating drying layer refers to a layer formed by coating the composition containing an inorganic solid electrolyte of the present invention and drying the dispersion medium (that is, a layer formed by using a composition containing an inorganic solid electrolyte of the present invention, and removing the composition of the dispersion medium from the composition containing an inorganic solid electrolyte of the present invention). The dispersion medium may remain in the active material layer and the dried coating layer within a range that does not impair the effects of the present invention, and the residual amount may be, for example, 3% by mass or less in each layer.
[0427] In the method for producing the sheet for an all-solid-state secondary battery of the present invention, each step such as coating and drying will be described below in the method for producing an all-solid-state secondary battery.
[0428] In the method for producing the all-solid-state secondary battery sheet of the present invention, the applied dried layer obtained in the above manner may be pressurized. The pressurization conditions and the like will be described in the method for producing the all-solid-state secondary battery described later.
[0429] Furthermore, in the method for producing the sheet for an all-solid-state secondary battery of the present invention, the substrate, the protective layer (particularly the release sheet), and the like can also be peeled off.
[0430] [All-solid-state secondary battery]
[0431] The all-solid-state secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The positive electrode active material layer is preferably formed on the positive electrode collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on the negative electrode collector and constitutes the negative electrode.
[0432] It is preferred that at least one of the negative electrode active material layer, the positive electrode active material layer and the solid electrolyte layer is formed by the composition containing an inorganic solid electrolyte of the present invention, and the negative electrode active material layer is formed by the composition containing an inorganic solid electrolyte of the present invention. It is also one of the preferred modes that all layers are formed by the composition containing an inorganic solid electrolyte of the present invention. For the types of components contained and their content ratios, the active material layer or solid electrolyte layer formed by the composition containing an inorganic solid electrolyte of the present invention is preferably the same as the solid component of the composition containing an inorganic solid electrolyte of the present invention. In addition, when the active material layer or the solid electrolyte layer is not formed by the composition containing an inorganic solid electrolyte of the present invention, known materials can be used.
[0433] The thickness of each of the negative electrode active material layer, the solid electrolyte layer and the positive electrode active material layer is not particularly limited. Considering the size of a general all-solid-state secondary battery, the thickness of each layer is preferably 10 to 1,000 μm, more preferably 20 μm or more and less than 500 μm. In the all-solid-state secondary battery of the present invention, the thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is further preferably 50 μm or more and less than 500 μm.
[0434] Each of the positive electrode active material layer and the negative electrode active material layer may include a current collector on the side opposite to the solid electrolyte layer.
[0435] <Frame>
[0436] The all-solid-state secondary battery of the present invention can be used as an all-solid-state secondary battery in the state of the above structure according to the purpose, but in order to make it in the form of a dry cell, it is preferably further enclosed in an appropriate shell for use. The shell can be a metallic shell or a resin (plastic) shell. In the case of using a metallic shell, for example, a shell made of aluminum alloy or stainless steel can be cited. Preferably, the metallic shell is divided into a positive electrode side shell and a negative electrode side shell and is electrically connected to the positive electrode collector and the negative electrode collector, respectively. Preferably, the shell on the positive electrode side is joined to the shell on the negative electrode side via a short circuit prevention gasket and becomes one.
[0437] Below, reference Figure 1 , an all-solid-state secondary battery according to a preferred embodiment of the present invention is described, but the present invention is not limited thereto.
[0438] Figure 1 It is a cross-sectional view schematically representing the all-solid-state secondary battery (lithium-ion secondary battery) involved in the preferred embodiment of the present invention. When observed from the negative electrode side, the all-solid-state secondary battery 10 of the present embodiment has a negative electrode collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode collector 5 in sequence. Each layer is in contact with each other and has an adjacent structure. By adopting such a structure, electrons (e-) are supplied to the negative electrode side during charging, and lithium ions (Li+) are accumulated there. On the other hand, during discharge, the lithium ions (Li+) accumulated in the negative electrode return to the positive electrode side and supply electrons to the working part 6. In the example shown in the figure, a light bulb is used as a model in the working part 6, and the light bulb is lit by discharge.
[0439] In will have Figure 1 When the all-solid-state secondary battery with the layer structure shown is placed in a 2032-type button-type battery box, the all-solid-state secondary battery is sometimes also referred to as a laminate for an all-solid-state secondary battery, and the battery produced by placing the all-solid-state secondary battery laminate in a 2032-type button-type battery box is called an all-solid-state secondary battery.
[0440] (Positive electrode active material layer, solid electrolyte layer, negative electrode active material layer)
[0441] In the all-solid-state secondary battery 10, the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer are all formed by the composition containing the inorganic solid electrolyte of the present invention. The all-solid-state secondary battery 10 shows excellent battery performance. The inorganic solid electrolyte, compound (SA) and polymer binder contained in the positive electrode active material layer 4, the solid electrolyte layer 3 and the negative electrode active material layer 2 can be the same type or different types.
[0442] In the present invention, either or both of the positive electrode active material layer and the negative electrode active material layer are referred to as active material layer or electrode active material layer. Also, either or both of the positive electrode active material and the negative electrode active material are referred to as active material or electrode active material.
[0443] In the present invention, when the constituent layers are formed from the composition containing the inorganic solid electrolyte of the present invention, an all-solid secondary battery having excellent cycle characteristics and low resistance can be realized.
[0444] In the all-solid-state secondary battery 10, the negative electrode active material layer can be set as a lithium metal layer. As the lithium metal layer, there can be cited a layer formed by stacking or molding lithium metal powder, lithium foil, and lithium vapor-deposited film. The thickness of the lithium metal layer is independent of the thickness of the negative electrode active material layer, and can be set to, for example, 1 to 500 μm.
[0445] The positive electrode current collector 5 and the negative electrode current collector 1 are preferably electron conductors.
[0446] In the present invention, either the positive electrode current collector or the negative electrode current collector, or both of them together, may be simply referred to as a current collector.
[0447] As the material forming the positive electrode collector, in addition to aluminum, aluminum alloy, stainless steel, nickel and titanium, it is preferred to treat the surface of aluminum or stainless steel with carbon, nickel, titanium or silver (material forming a thin film), among which aluminum and aluminum alloy are more preferred.
[0448] As the material for forming the negative electrode collector, in addition to aluminum, copper, copper alloys, stainless steel, nickel and titanium, it is preferred to use a material in which the surface of aluminum, copper, copper alloys or stainless steel is treated with carbon, nickel, titanium or silver, and aluminum, copper, copper alloys and stainless steel are more preferred.
[0449] The shape of the current collector is generally a film sheet, but a mesh, a perforated body, a lath body, a porous body, a foamed body, a molded body of a fiber group, or the like may also be used.
[0450] The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm. It is also preferred that the surface of the current collector be provided with irregularities by surface treatment.
[0451] In the above-described all-solid-state secondary battery 10 , the positive electrode active material layer can also be formed of a layer formed of a known constituent layer forming material.
[0452] In the present invention, functional layers, components, etc. may be appropriately inserted or arranged between or outside the negative electrode collector, the negative electrode active material layer, the solid electrolyte layer, the positive electrode active material layer, and the positive electrode collector. Furthermore, each layer may be configured as a single layer or as a multilayer.
[0453] [Manufacturing of all-solid-state secondary batteries]
[0454] The all-solid-state secondary battery can be manufactured by a conventional method. Specifically, the all-solid-state secondary battery can be manufactured by forming the above-mentioned layers using the composition containing the inorganic solid electrolyte of the present invention. This will be described in detail below.
[0455] The all-solid-state secondary battery of the present invention can be manufactured by a method (manufacturing method of a sheet for an all-solid-state secondary battery of the present invention) comprising (via) a step of appropriately coating the composition containing an inorganic solid electrolyte of the present invention on a substrate (e.g., a metal foil serving as a current collector) to form a coating (film formation).
[0456] For example, a composition containing an inorganic solid electrolyte as a positive electrode material (positive electrode composition) and containing a positive electrode active material is applied to a metal foil as a positive electrode collector to form a positive electrode active material layer to make a positive electrode sheet for an all-solid-state secondary battery. Next, a composition containing an inorganic solid electrolyte for forming a solid electrolyte layer is applied to the positive electrode active material layer to form a solid electrolyte layer. In addition, a negative electrode active material layer is formed by applying a composition containing an inorganic solid electrolyte as a negative electrode material (negative electrode composition) on the solid electrolyte layer. By overlapping the negative electrode collector (metal foil) on the negative electrode active material layer, an all-solid-state secondary battery with a structure in which a solid electrolyte layer is sandwiched between the positive electrode active material layer and the negative electrode active material layer can be obtained. It can also be enclosed in a shell as a desired all-solid-state secondary battery.
[0457] Furthermore, in contrast to the method of forming each layer, an all-solid-state secondary battery can be manufactured by forming a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer on a negative electrode collector and stacking the positive electrode collector.
[0458] As other methods, the following methods can be cited. That is, a positive electrode sheet for an all-solid-state secondary battery is prepared as described above. Furthermore, a composition containing an inorganic solid electrolyte as a negative electrode material (negative electrode composition) and containing a negative electrode active material is applied to a metal foil as a negative electrode collector to form a negative electrode active material layer to prepare a negative electrode sheet for an all-solid-state secondary battery. Next, on the active material layer of any one of these sheets, a solid electrolyte layer is formed as described above. Furthermore, on the solid electrolyte layer, another of the positive electrode sheet for an all-solid-state secondary battery and the negative electrode sheet for an all-solid-state secondary battery are stacked in such a manner that the solid electrolyte layer is in contact with the active material layer. In this way, an all-solid-state secondary battery can be manufactured.
[0459] Furthermore, as other methods, the following methods can be cited. That is, a positive electrode sheet for an all-solid-state secondary battery and a negative electrode sheet for an all-solid-state secondary battery are prepared as described above. In addition, a solid electrolyte sheet for an all-solid-state secondary battery consisting of a solid electrolyte layer is prepared by applying a composition containing an inorganic solid electrolyte to a substrate. Moreover, the solid electrolyte layer peeled off from the substrate is sandwiched by a positive electrode sheet for an all-solid-state secondary battery and a negative electrode sheet for an all-solid-state secondary battery. In this way, an all-solid-state secondary battery can be manufactured.
[0460] In addition, as described above, a positive electrode sheet for an all-solid-state secondary battery or a negative electrode sheet for an all-solid-state secondary battery and a solid electrolyte sheet for an all-solid-state secondary battery are made. Then, the positive electrode sheet for an all-solid-state secondary battery or the negative electrode sheet for an all-solid-state secondary battery and the solid electrolyte sheet for an all-solid-state secondary battery are overlapped and pressurized in a state where the positive electrode active material layer or the negative electrode active material layer is in contact with the solid electrolyte layer. In this way, the solid electrolyte layer is transferred to the positive electrode sheet for an all-solid-state secondary battery or the negative electrode sheet for an all-solid-state secondary battery. Then, the solid electrolyte layer obtained by peeling off the substrate of the solid electrolyte sheet for an all-solid-state secondary battery and the negative electrode sheet for an all-solid-state secondary battery or the positive electrode sheet for an all-solid-state secondary battery (in a state where the negative electrode active material layer or the positive electrode active material layer is in contact with the solid electrolyte layer) are overlapped and pressurized. In this way, an all-solid-state secondary battery can be manufactured. There is no particular limitation on the pressurization method and pressurization conditions in the method, and the method and pressurization conditions described in the pressurization of the composition to be applied later can be applied.
[0461] The solid electrolyte layer and the like can also be formed by, for example, forming a composition containing an inorganic solid electrolyte on a substrate or an active material layer by press molding under pressurization conditions described below, or a sheet molded body of a solid electrolyte or active material can be used.
[0462] In the above-mentioned manufacturing method, the composition containing an inorganic solid electrolyte of the present invention can be used for any one of the positive electrode composition, the composition containing an inorganic solid electrolyte and the negative electrode composition. It is preferred to use the composition containing an inorganic solid electrolyte of the present invention for the negative electrode composition, and the composition containing an inorganic solid electrolyte of the present invention can also be used for any composition.
[0463] When a solid electrolyte layer or an active material layer is formed by a composition other than the solid electrolyte composition of the present invention, a commonly used composition can be cited as its material. In addition, when manufacturing an all-solid-state secondary battery, no negative electrode active material layer is formed, and ions of metals belonging to Group 1 or Group 2 of the periodic table accumulated in the negative electrode collector by initialization or charging during use described later are combined with electrons and precipitated as metal on the negative electrode collector, etc., thereby forming a negative electrode active material layer.
[0464] <Formation of each layer (film formation)>
[0465] The method for coating the composition containing the inorganic solid electrolyte is not particularly limited and can be appropriately selected, and examples thereof include coating (preferably wet coating), spray coating, spin coating, dip coating, slit coating, stripe coating, and bar coating.
[0466] At this time, the composition containing the inorganic solid electrolyte can be dried after being coated separately, or it can be dried after being coated in multiple layers. There is no particular restriction on the drying temperature. The lower limit is preferably above 30°C, more preferably above 60°C, and more preferably above 80°C. The upper limit is preferably below 300°C, more preferably below 250°C, and more preferably below 200°C. By heating within such a temperature range, the dispersion medium can be removed to obtain a solid state (coating dry layer). Moreover, the temperature will not be too high and the components of the all-solid-state secondary battery will not be damaged, so it is preferred. As a result, in the all-solid-state secondary battery, excellent overall performance is exhibited and good adhesion and good ion conductivity can be obtained without pressurization.
[0467] Preferably, after applying the composition containing the inorganic solid electrolyte, each layer or the all-solid-state secondary battery is pressurized after the layers are stacked or after the all-solid-state secondary battery is made. As a pressurization method, a hydraulic cylinder punching machine or the like can be cited. There is no particular limitation on the pressure, but it is usually preferably in the range of 5 to 1500 MPa.
[0468] Furthermore, the applied composition containing an inorganic solid electrolyte may be heated while being pressurized. The heating temperature is not particularly limited, but is generally in the range of 30 to 300°C. Pressing may also be performed at a temperature higher than the glass transition temperature of the inorganic solid electrolyte. In addition, pressing may also be performed at a temperature higher than the glass transition temperature of the polymer contained in the binder. However, the temperature is generally not higher than the melting point of the polymer.
[0469] The pressurization may be performed in a state where the coating solvent or dispersion medium is dried in advance, or may be performed in a state where the solvent or dispersion medium remains.
[0470] In addition, the respective compositions may be applied simultaneously, or applied, dried, and pressed simultaneously and / or sequentially. After being applied to respective substrates, the compositions may be laminated by transfer.
[0471] The environment in the manufacturing process, such as heating or pressurizing, is not particularly limited and may be any environment such as atmospheric pressure, dry air (dew point -20°C or less), or inert gas (e.g., argon, helium, or nitrogen).
[0472] The punching time can be a short time (e.g., within a few hours) to apply high pressure, or a long time (more than 1 day) to apply moderate pressure. In addition to the sheet for all-solid-state secondary batteries, for example, in the case of all-solid-state secondary batteries, it is possible to use a restraining tool (screw tightening pressure, etc.) of the all-solid-state secondary battery to continuously apply moderate pressure.
[0473] The pressing pressure may be uniform or different relative to the pressure receiving portion such as the sheet surface.
[0474] The pressing pressure can be changed according to the area or layer thickness of the pressure receiving portion, and the same portion can also be changed in stages with different pressures.
[0475] The stamping surface can be smooth or rough.
[0476] <Initialization>
[0477] The all-solid-state secondary battery manufactured in the above manner is preferably initialized after manufacturing or before use. There is no particular limitation on initialization, for example, initial charging and discharging can be performed under an increased stamping pressure, and then the pressure is released until the general use pressure of the all-solid-state secondary battery is reached.
[0478] [Applications of all-solid-state secondary batteries]
[0479] The all-solid-state secondary battery of the present invention can be applied to a variety of purposes. The applicable mode is not particularly limited. For example, when it is mounted on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone sub-machine, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a camcorder, a liquid crystal television, a portable vacuum cleaner, a portable CD, a small disk, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, etc. As other civilian products, automobiles, electric vehicles, motors, lighting fixtures, toys, game consoles, load regulators, clocks, flashlights, cameras, and medical equipment (pacemakers, hearing aids, and shoulder massagers, etc.) can be listed. Moreover, it can be used as various military products and aviation products. Moreover, it can also be combined with solar cells.
[0480] Example
[0481] The present invention will be described in further detail below with reference to the Examples, but the present invention is not limited thereto and should not be construed. In the following Examples, "parts" and "%" representing the composition are by mass unless otherwise specified. In the present invention, "room temperature" means 25°C.
[0482] 1. Synthesis of sulfide-based inorganic solid electrolytes
[0483] [Synthesis Example A]
[0484] The sulfide-based inorganic solid electrolyte was synthesized with reference to the non-patent literature of T. Ohtomo, A. Hayashi, M. Tatsumisago, Y. Tsuchida, S. Hama, K. Kawamoto, Journal of Power Sources, 233, (2013), pp231-235 and A. Hayashi, S. Hama, H. Morimoto, M. Tatsumisago, T. Minami, Chem. Lett., (2001), pp872-873.
[0485] Specifically, 2.42 g of lithium sulfide (Li2S, manufactured by Aldrich. Inc., purity>99.98%) and 3.90 g of phosphorus pentasulfide (P2S5, manufactured by Aldrich. Inc., purity>99%) were weighed in a glove box under an argon atmosphere (dew point -70°C), put into an agate mortar, and mixed for 5 minutes using an agate pestle. The mixing ratio of Li2S and P2S5 was Li2S:P2S5=75:25 in terms of molar ratio.
[0486] Next, 66 zirconia beads with a diameter of 5 mm were added to a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), and the total amount of the mixture of the above-mentioned lithium sulfide and phosphorus pentasulfide was added, and the container was sealed under an argon atmosphere. The container was set in a planetary ball mill P-7 (trade name, manufactured by Fritsch Co., Ltd.), and mechanical grinding was performed at a temperature of 25°C and a rotation speed of 510 rpm for 20 hours to obtain 6.20 g of a yellow powder of a sulfide-based inorganic solid electrolyte (Li-PS-based glass, hereinafter sometimes marked as LPS). The ion conductivity was 0.28 mS / cm, and the average particle size of the Li-PS-based glass based on the above-mentioned measurement method was 15 μm.
[0487] 2. Synthesis or preparation of compound (SA)
[0488] Compounds (SA) A-1 to A-28, B-01 to B-02, and C-01 to C-04 shown below were respectively dissolved in toluene (dispersion medium) to prepare solutions having a concentration of 3% by mass.
[0489] [Chemical formula 12]
[0490]
[0491] [Chemical formula 13]
[0492]
[0493] [Chemical formula 14]
[0494]
[0495] Each of the compounds represented by the above A-01 to A-28 is a compound represented by the above formula (1).
[0496] <Preparation or synthesis of each compound>
[0497] (1) Compounds A-01 to A-04 and A-20 to A-24
[0498] As each compound, a commercially available compound (manufactured by FUJIFILM Wako Pure Chemical Corporation) was used.
[0499] (2) Compound A-05
[0500] Compound A-05 was synthesized according to the method described in the following document.
[0501] Reference: Analytical Chemistry, 1998, vol.60, 2509-2512
[0502] (3) Compounds A-06 to A-18
[0503] Compounds A-06 to A-18 were synthesized in the same manner as A-05, except that the alcohol compound and the acid anhydride used to form A-06 to A-18 were changed in the synthesis of compound A-05.
[0504] (4) Compound A-19
[0505] The synthesis was carried out according to the method described in the following document.
[0506] Literature: Journal of the American Society for Mass Spectrometry, 2014, vol.25, 751-757
[0507] (5) Compounds A-25 to A-28
[0508] Compounds A-25 to A-28 were synthesized according to the methods described in the following documents.
[0509] (Compound A-25) Literature: Organic and Biomolecular Chemistry, 2014, vol.12, 261-264
[0510] (Compound A-26) Reference: Molecules, 2016, vol. 21(1), 24
[0511] (Compound A-27) Literature: Bulletin de la Societe Chimique de France, 1988, 671-680
[0512] (Compound A-28) Literature: Tetrahedron Letters, 1986, vol. 27, 6329-6332
[0513] As the compound (B) (fluorine-based polymer), the following compounds B-01 and B-02 were prepared.
[0514] B-01: Fluorolink (registered trademark) F10 (perfluoropolyether, containing phosphoric acid group, manufactured by Solvey)
[0515] B-02: Fluorolink (registered trademark) S10 (perfluoropolyether, containing alkoxysilyl groups, manufactured by Solvey)
[0516] As the compound (C) (organopolysiloxane), the following compounds C-01 to C-04 were prepared.
[0517] C-01: X-22-162C (reactive silicone oil at both ends, reactive group is carboxyl group, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0518] C-02: X-22-163A (reactive silicone oil at both ends, reactive group is epoxy group, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0519] C-03: X-22-164C (reactive silicone oil at both ends, reactive group is methacryloyloxy, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0520] C-04: KF-2201 (side chain reactive silicone oil, reactive group is (phenolic) hydroxyl group, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0521] [Example 1]
[0522] <Preparation of Negative Electrode Compositions S-1 to S-44 and cS-1 to cS-3>
[0523] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), 180 zirconium oxide beads with a diameter of 5 mm were placed, and 4.0 g of the LPS synthesized in the above-mentioned Synthesis Example A, a solution of the compound (SA) shown in Table 1 having an amount (solid content) shown in Table 1, and 22 g of butyl butyrate were placed. The container was set in a planetary ball mill P-7 (trade name) manufactured by Fritsch Co., Ltd., and stirred at 25° C. and 300 rpm for 60 minutes. Then, 5.3 g of silicon (Si, manufactured by Aldrich) or graphite (CGB20, trade name, manufactured by Nippon Graphite Industries, Co., Ltd.) as a negative electrode active material, acetylene black (manufactured by Denka Company Limited) as a conductive aid in an amount shown in Table 1, and a butyl butyrate dispersion of a binder PVdF-HFP (manufactured by Arkema SA, KYNERFLEX 2500-20) in an amount shown in Table 1 (solid content) were added, and the container was set in a planetary ball mill P-7, and mixed at 25° C. at a rotation speed of 100 rpm for 10 minutes. In this way, negative electrode compositions S-1 to S-44 and cS-1 to cS-3 were prepared as non-aqueous compositions.
[0524] <Preparation of negative electrode composition S-45>
[0525] In the preparation of the above-mentioned negative electrode composition S-3, the binder PVdF-HFP was changed to the polyurethane binder B-1 synthesized in the following synthesis example 1, and the mixing amount of the binder and the mixing amount of butyl butyrate were adjusted so that the solid content became the same. Otherwise, the negative electrode composition S-45 was prepared as a non-aqueous composition in the same manner as the preparation of the above-mentioned negative electrode composition S-3.
[0526] [Chemical formula 15]
[0527]
[0528] [Synthesis Example 1: Synthesis of Polyurethane B-1 and Preparation of Binder Dispersion Liquid B-1 Composed of Polyurethane B-1]
[0529] (Synthesis of Polyurethane B-1)
[0530] In a 300 mL three-necked flask, 2.92 g of polyethylene glycol (PEG200 (trade name), number average molecular weight 200, manufactured by FUJIFILM Wako Pure Chemical Corporation), 3.65 g of polytetramethylene ether glycol (number average molecular weight 250, manufactured by SIGMA-Aldrich), 3.78 g of NISSO-PB G-1000 (trade name, manufactured by Nippon Soda Co., Ltd.), and 0.60 g of 2,2-bis(hydroxymethyl)butyric acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added and dissolved in 80.85 g of THF (tetrahydrofuran). 9.26 g of diphenylmethane diisocyanate (manufactured by FUJIFILM Wako Pure Chemical Corporation) was added to the solution and stirred at 60° C. to uniformly dissolve the mixture.
[0531] To the obtained solution, 65 mg of NEOSTANNU-600 (trade name, manufactured by Nitto Kasei Co., Ltd.) was added, and the mixture was stirred at 60° C. for 5 hours. To the solution, 0.96 g of methanol was added to seal the polymer terminal to terminate the polymerization reaction, thereby obtaining a 20 mass % THF solution of polymer B-1 (polymer solution).
[0532] (Preparation of Binder Dispersion B-1)
[0533] 15.00 g of the polymer solution obtained above was diluted with 15.00 g of THF, and 90.00 g of butyl butyrate was added dropwise over 1 hour while stirring to obtain an emulsion of polymer B-1. The emulsion was concentrated to about 70 g, and butyl butyrate was added to obtain a 3% by mass butyl butyrate dispersion of a binder composed of polymer B-1 (binder dispersion B-1) by setting the total amount to 100.00 g.
[0534] <Manufacturing of negative electrode sheets for all-solid-state secondary batteries>
[0535] Each negative electrode composition obtained above was applied to a stainless steel foil (negative electrode collector) having a thickness of 10 μm using a baking applicator (trade name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), heated at 100°C for 2 hours, and dried (dispersion medium removed) the negative electrode composition. Then, using a hot press, the dried negative electrode composition was pressed at 25°C (20 MPa, 1 minute), and all-solid-state secondary battery negative electrode sheets PS-1 to PS-45 and PcS-1 to PcS-3 having a negative electrode active material layer having a thickness of 50 μm were produced.
[0536] The compound used for preparing the negative electrode composition cS-2 and the negative electrode sheet PcS-2 for the all-solid-state secondary battery (chemical structure is shown below). cA-01 is not the compound (SA) specified in the present invention, but in Table 1, it is shown in the compound (SA) column for convenience.
[0537] [Chemical formula 16]
[0538]
[0539] [Table 1]
[0540]
[0541] <Notes on the table>
[0542] The content is the content in 100% by mass of the solid content of the negative electrode composition, and the unit is mass %.
[0543] The conductive auxiliary agent was acetylene black (manufactured by Denka Company Limited).
[0544] The adhesive was a polymer adhesive composed of PVdF-HFP or a polyurethane adhesive B-1.
[0545] <Preparation of a composition containing an inorganic solid electrolyte>
[0546] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), 180 zirconium oxide beads with a diameter of 5 mm were added, and 4.85 g of LPS synthesized in the above-mentioned Synthesis Example A, 0.15 g (solid content mass) of the following polymer binder solution, and 16.0 g of butyl butyrate were added. Then, the container was set in a planetary ball mill P-7 manufactured by Fritsch Co., Ltd., and mixed at a temperature of 25° C. and a rotation speed of 150 rpm for 10 minutes, thereby preparing a composition containing an inorganic solid electrolyte.
[0547] (Polymer Binder)
[0548] A polymer binder solution having a solid content concentration of 3% by mass was prepared by dissolving PVdF-HFP (KYNER FLEX 2500-20 manufactured by Arkema SA) in butyl butyrate.
[0549] <Manufacturing of solid electrolyte sheets for all-solid-state secondary batteries>
[0550] The composition containing the inorganic solid electrolyte obtained above was applied to an aluminum foil having a thickness of 20 μm using a baking applicator (trade name: SA-201), heated at 80°C for 2 hours, and dried (removed the dispersion medium) containing the composition containing the inorganic solid electrolyte. Then, a hot press was used to heat and pressurize the dried composition containing the inorganic solid electrolyte for 10 seconds at a temperature of 120°C and a pressure of 600 MPa, thereby producing a solid electrolyte sheet for an all-solid-state secondary battery. The thickness of the solid electrolyte layer was 50 μm.
[0551] <Manufacturing of negative electrode sheet for all-solid-state secondary battery having solid electrolyte layer>
[0552] On the negative electrode active material layer of each all-solid-state secondary battery negative electrode sheet shown in Table 2, the above-made all-solid-state secondary battery solid electrolyte sheet was stacked so that the solid electrolyte layer was in contact with the negative electrode active material layer, and after being pressed and transferred (stacked) at a temperature of 25°C and a pressure of 50MPa using a punch, it was further pressed at a temperature of 25°C and a pressure of 600MPa. In this way, a solid electrolyte layer with a thickness of 50μm was stacked on the negative electrode active material layer of the all-solid-state secondary battery negative electrode sheet.
[0553] <Preparation of positive electrode composition>
[0554] Into a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), 180 zirconia beads with a diameter of 5 mm were added, and 2.8 g of LPS synthesized in the above-mentioned Synthesis Example A, 0.2 g (solid content mass) of the following polymer binder solution, and 22 g of butyl butyrate were added. The container was set in a planetary ball mill P-7 manufactured by Fritsch Co., Ltd. and stirred at 25°C and 300 rpm for 60 minutes. Then, 7.0 g of LiNi was added as a positive electrode active material into the container. 1 / 3 Co 1 / 3Mn 1 / 3 O2 (NMC, manufactured by Aldrich, CO. LTD.) was placed in a planetary ball mill P-7 in the same manner, and mixed at 25° C. and 100 rpm for 5 minutes. In this way, a positive electrode composition was prepared.
[0555] (Binder solution)
[0556] A polymer binder solution having a solid content concentration of 3% by mass was prepared by dissolving PVdF-HFP (KYNER FLEX 2500-20 manufactured by Arkema SA) in butyl butyrate.
[0557] <Manufacturing of positive electrode sheets for all-solid-state secondary batteries>
[0558] The positive electrode composition obtained above was applied to an aluminum foil (positive electrode collector) having a thickness of 20 μm using a baking applicator (trade name: SA-201), heated at 100°C for 2 hours, and dried (to remove the dispersion medium) the positive electrode composition. Then, using a hot press, the dried positive electrode composition was pressed at 25°C (10 MPa, 1 minute) to produce a positive electrode sheet for an all-solid-state secondary battery having a positive electrode active material layer having a thickness of 80 μm.
[0559] The produced positive electrode sheet for the all-solid-state secondary battery was punched into a disk shape with a diameter of 14.0 mm to obtain a disk-shaped positive electrode sheet.
[0560] <Manufacturing of all-solid-state secondary batteries>
[0561] Each of the prepared negative electrode sheets for all-solid-state secondary batteries having a solid electrolyte layer (the aluminum foil of the solid electrolyte sheet for all-solid-state secondary batteries has been peeled off) was cut into a disk shape with a diameter of 14.5 mm. Figure 2 As shown, place the assembly with spacers and washers (in Figure 2 In a stainless steel 2032 type button battery case 11 (not shown in the figure), the negative electrode collector of the cut disc-shaped sheet is placed at the bottom. A disc-shaped positive electrode sheet is stacked on the solid electrolyte layer of the disc-shaped sheet so that the solid electrolyte layer is in contact with the positive electrode active material layer, thereby forming a laminate 12 for an all-solid-state secondary battery (a laminate consisting of aluminum foil-positive electrode active material layer-solid electrolyte layer-negative electrode active material layer-stainless steel foil). Then, the 2032 type button battery case 11 is crimped, thereby respectively manufacturing Figure 2 The all-solid-state secondary batteries No. 1 to 45 and c1 to c3 shown in the figure. The all-solid-state secondary batteries manufactured in this way have Figure 1 The layer structure shown.
[0562] The following characteristics were evaluated for the manufactured all-solid-state secondary batteries Nos. 1 to 45 and c1 to c3, and the results are shown in Table 2.
[0563] Table 2 calculates and shows the ratio of the content [SE] of the inorganic solid electrolyte to the content [SA] of the compound (SA) in 100% by mass of the solid content of the composition containing the inorganic solid electrolyte (negative electrode active material layer): [SA] / [SE] and the ratio of the content [BR] of the polymer binder to the content [SA] of the compound (SA): [BR] / [SA].
[0564] In addition, the compound described in the column of "Compound (SA)" in Table 2 indicates the compound (SA) contained in the negative electrode active material layer.
[0565] <Evaluation 1: Layer density test>
[0566] Solid electrolyte molded body particles for evaluation were prepared using the compounds (SA) corresponding to the respective all-solid-state secondary batteries shown in Table 2 by the following procedure.
[0567] Specifically, 3.0 g of zirconia beads with a diameter of 3 mm were put into a 5 mL centrifuge tube, and LPS (0.8 g) synthesized in the above-mentioned synthesis example A, a butyl butyrate solution or dispersion (8.2 mg (solid content mass)) of the compound (SA) for making each all-solid-state secondary battery shown in Table 2, and butyl butyrate (adjusted to an amount in which the solid content concentration of the obtained composition containing an inorganic solid electrolyte reaches 20% by mass) were put in. Then, the centrifuge tube was placed in a test tube mixer Se-04 (trade name, made by TIETECH Co., Ltd.) and mixed for 30 minutes to prepare a composition containing an inorganic solid electrolyte. The obtained composition containing an inorganic solid electrolyte was recovered into an aluminum cup and dried on a hot plate at 100 ° C for 2 hours to obtain a powder of the composition containing an inorganic solid electrolyte. The obtained powder was pressed at 25° C. and a pressure of 200 MPa or 600 MPa using a punch press to produce solid electrolyte molded body particles for evaluation (film thickness of 300 to 500 μm).
[0568] Next, the total thickness of the pellets after molding was measured and the volume was estimated, and the layer density of each of the produced solid electrolyte molded body pellets for evaluation was calculated by powder mass / particle volume.
[0569] The layer density D of the solid electrolyte molded body particles for evaluation prepared by using the same compound (SA) and pressed at a pressure of 200 MPa was calculated. 200 The layer density D of the pellets produced by pressing at a pressure of 600 MPa is 600 Ratio: D 200 / D 600 .
[0570] In this test, the ratio: D 200 / D 600 The closer to 1, the smaller the surface resistance of the inorganic solid electrolytes. It is believed that when used in the constituent layer of an all-solid-state secondary battery, even if it expands temporarily, it is easy to shrink into a dense constituent layer (a constituent layer with few gaps) before expansion. The following evaluation standard "C" or above is the qualified level of this test. The results are shown in Table 3.
[0571] -Evaluation Criteria-
[0572] A: 0.9≤D 200 / D 600 <1.0
[0573] B: 0.8≤D 200 / D 600 <0.9
[0574] C: 0.7 ≤ D 200 / D 600 <0.8
[0575] D:D 200 / D 600 <0.7
[0576] <Evaluation 2: Evaluation of active material capacity>
[0577] As the battery characteristics of all-solid-state secondary batteries No. 1 to 45 and c1 to c3, the theoretical capacity of the active material was calculated and evaluated as follows: A higher capacity means a higher energy density.
[0578] -Calculation of theoretical capacity-
[0579] Calculated from the saturation composition upon lithium insertion.
[0580] Graphite: Since graphite is converted from C to LiC6, the amount of Li inserted per 1 g of graphite becomes 1340 (coulombs) ([(1 (g) / 6 (the amount of Li inserted per 1 molecule of graphite)) / 12 (molecular weight of graphite)]×96500 (Faraday constant)).
[0581] Since 3.6 coulombs is 1 mAh, the theoretical capacity of graphite is 372 (mAh / g) (1340 / 3.6).
[0582] Silicon: Since silicon changes from Si to Li 4.4 Si, therefore, the amount of Li inserted per 1 g of silicon is 15110 (coulombs) ([(1 (g) × 4.4 (Li inserted per 1 molecule of silicon)) / 28.1 (silicon molecular weight)] × 96500 (Faraday constant)).
[0583] Therefore, the theoretical capacity of silicon is 4197 (mAh / g) (15110 / 3.6).
[0584] -Evaluation Criteria-
[0585] A: 1500mAh / g≤theoretical capacity of active material
[0586] B: 400mAh / g≤theoretical capacity of active material<1500mAh / g
[0587] C: Theoretical capacity of active material <400mAh / g
[0588] <Evaluation 3: Evaluation of resistance>
[0589] As battery characteristics of all-solid-state secondary batteries No. 1 to 45 and c1 to c3, the resistances thereof were measured, and the level of the battery resistance was evaluated.
[0590] The resistance of each all-solid-state secondary battery was evaluated using a charge and discharge evaluation device: TOSCAT-3000 (trade name, manufactured by TOYO SYSTEM Co., Ltd.). Charging was performed until the current density reached 0.1 mA / cm 2 The battery voltage reaches 4.2 V. Discharge is continued until the current density reaches 0.2 mA / cm 2 And the battery voltage reaches 2.5V. This one charge and one discharge is regarded as one charge and discharge cycle and two cycles of charge and discharge are repeated. The battery voltage after discharge of 5mAh / g (electricity per 1g of active material mass) in the second cycle is read. The battery voltage is included in which of the following evaluation criteria to evaluate the resistance of the all-solid-state secondary battery.
[0591] In the present invention, a higher battery voltage means a lower resistance, and an evaluation standard of "C" or higher is considered acceptable.
[0592] -Evaluation Criteria-
[0593] A: 4.0V≤battery voltage
[0594] B: 3.7V≤Battery voltage<4.0V
[0595] C: 3.5V≤Battery voltage<3.7V
[0596] D: 2.5V≤Battery voltage<3.5V
[0597] E: Unable to charge or discharge
[0598] <Evaluation 4: Evaluation of cycle characteristics>
[0599] As battery characteristics of all-solid-state secondary batteries No. 1 to 45 and c1 to c3, the discharge capacity retention ratio was measured and the cycle characteristics were evaluated.
[0600] Specifically, the discharge capacity maintenance rate of each all-solid-state secondary battery was measured in an environment of 25° C. using a charge and discharge evaluation device: TOSCAT-3000 (trade name, manufactured by TOYO SYSTEM Co., Ltd.). Charging was performed until the current density reached 0.1 mA / cm 2 The battery voltage reaches 4.2 V. Discharge is continued until the current density reaches 0.1 mA / cm 2 And the battery voltage reached 2.5 V. This one charge and one discharge is regarded as one charge and discharge cycle, and one cycle of charge and discharge is performed to initialize the all-solid secondary battery.
[0601] For the all-solid-state secondary battery after initialization, repeated charging and discharging were performed under the same conditions as the above-mentioned charging and discharging conditions. When the discharge capacity (initial discharge capacity) of the first cycle of charging and discharging after initialization is set to 100%, the number of charging and discharging cycles when the discharge capacity retention rate (discharge capacity relative to the initial discharge capacity) reaches (decreases to) 75% is evaluated by including which of the following evaluation criteria to evaluate the cycle characteristics.
[0602] In this test, the more charge and discharge cycles there are, the better the battery performance (cycle characteristics), and the battery can maintain its initial performance even after repeated charge and discharge (even after long-term use). The following evaluation criteria "C" or above are considered pass in this test.
[0603] In addition, the initial discharge capacities of all-solid-state secondary batteries Nos. 1 to 45 all showed sufficient values to function as all-solid-state secondary batteries.
[0604] -Evaluation Criteria-
[0605] (1) When silicon is used as the negative electrode active material
[0606] A: 100 cycles ≤ number of charge and discharge cycles
[0607] B: 50 cycles ≤ charging and discharging cycles < 100 cycles
[0608] C: 10 cycles ≤ charging and discharging cycles < 50 cycles
[0609] D: Number of charge and discharge cycles < 10 cycles
[0610] (2) When graphite is used as the negative electrode active material
[0611] A: 500 cycles ≤ number of charge and discharge cycles
[0612] B: 200 cycles ≤ charging and discharging cycles < 500 cycles
[0613] C: 100 cycles ≤ charging and discharging cycles < 200 cycles
[0614] D: Number of charge and discharge cycles < 100 cycles
[0615] [Table 2]
[0616]
[0617] From the results shown in Table 2, the following can be understood.
[0618] It can be seen that for the inorganic solid electrolyte and the comparative example of the compound other than the compound (SA) specified in the present invention or the comparative example of the above-mentioned compound (SA) not used in combination, the composition containing the inorganic solid electrolyte has a small layer density ratio, so if high pressure is not applied, a dense constituent layer cannot be formed, and the temporarily expanded constituent layer is difficult to shrink into a dense constituent layer before expansion. The all-solid-state secondary battery having a comparative example of a constituent layer formed by these compositions containing inorganic solid electrolytes cannot take into account both resistance and cycle characteristics.
[0619] In contrast, it is known that for an inorganic solid electrolyte and a compound (SA) specified in the present invention, the composition containing an inorganic solid electrolyte of the present invention is large in layer density ratio, so it is not significantly affected by the height of the pressure and can form a dense constituent layer, and the temporarily expanded constituent layer is easily contracted into a dense constituent layer before expansion. It is known that the all-solid-state secondary battery of the present invention having a constituent layer formed by these compositions containing inorganic solid electrolytes can simultaneously achieve low resistance and excellent cycle characteristics. In particular, even if Si with large expansion and contraction caused by charge and discharge is used as a negative electrode active material, a high active material capacity is also shown, and low resistance and excellent cycle characteristics can be taken into account. Therefore, it is known that even in a composition containing an inorganic solid electrolyte containing a common active material or not containing an active material, it is easy to return to a dense constituent layer, and low resistance and excellent cycle characteristics can be given to the all-solid-state secondary battery.
[0620] The present invention has been described together with its embodiments, but unless otherwise specified, the present invention is not limited in any detail in the description and should be interpreted broadly without departing from the gist and scope of the invention set forth in the claims.
[0621] This application claims priority based on Japanese Patent Application No. 2019-177551 filed in Japan on September 27, 2019, which are hereby incorporated by reference, and the contents thereof are incorporated into this specification as a part of what is described in this specification.
[0622] Explanation of symbols
[0623] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state secondary battery, 11-2032 type button battery shell, 12-laminated body for all-solid-state secondary battery, 13-button-type all-solid-state secondary battery.
Claims
1. A composition containing an inorganic solid electrolyte for an all-solid-state secondary battery that does not contain an organic electrolyte salt, comprising: an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, an active material, and at least one compound (SA) selected from the following (A) to (C), in, The total content of the inorganic solid electrolyte and the active material is 50% by mass or more in 100% by mass of the solid content of the composition containing the inorganic solid electrolyte. The active material is a positive electrode active material or a negative electrode active material. When the active material is a positive electrode active material, its content in the composition containing an inorganic solid electrolyte is 30 to 95% by mass; when the active material is a negative electrode active material, its content in the composition containing an inorganic solid electrolyte is 30 to 80% by mass. (A): A compound represented by the following formula (1) Formula (1) RAX In formula (1), R represents a group including a fluorinated hydrocarbon group and a hydrocarbon group having no fluorine atom, A represents a divalent linking group not including an aromatic ring structure, and X represents a functional group represented by the following functional group group (I). (B): perfluoropolyether, polychlorotrifluoroethylene or polytetrafluoroethylene, wherein the perfluoropolyether, polychlorotrifluoroethylene or polytetrafluoroethylene has a phosphoric acid group or an alkoxysilyl group among the functional groups included in the following functional group group (I); (C): an organopolysiloxane having at least one functional group among the functional groups included in the following functional group group (I): <Functional group (I)> An acidic group, a group having a basic nitrogen atom, an amide group, a urea group, a urethane group, an alkoxysilyl group, an epoxy group, an isocyanate group, a hydroxyl group or a (meth)acryloyloxy group.
2. The composition containing an inorganic solid electrolyte according to claim 1, wherein [SA] / [SE] is 0.0003~0.11, The [SA] / [SE] is the ratio of the content [SE] of the inorganic solid electrolyte to the total content [SA] of the compound (SA) in 100% by mass of the solid content of the composition containing the inorganic solid electrolyte.
3. The composition containing an inorganic solid electrolyte according to claim 1, wherein The organopolysiloxane (C) has a carboxyl group, an epoxy group, a methacryloxy group or a hydroxyl group among the functional groups included in the functional group group (I). The inorganic solid electrolyte-containing composition according to claim 1 , comprising a polymer binder.
5. The composition containing an inorganic solid electrolyte according to claim 4, wherein [BR] / [SA] is 0.2 to 5, The [BR] / [SA] is the ratio of the content [BR] of the polymer binder to the total content [SA] of the compound (SA) in 100% by mass of the solid content of the composition containing the inorganic solid electrolyte.
6. The composition containing an inorganic solid electrolyte according to claim 1, wherein The active material is an active material containing silicon or tin.
7. The composition containing an inorganic solid electrolyte according to claim 1, wherein The compound (SA) includes a compound represented by the formula (1).
8. The composition containing an inorganic solid electrolyte according to claim 1, wherein The inorganic solid electrolyte is a sulfide-based inorganic solid electrolyte. 9 . The inorganic solid electrolyte-containing composition according to claim 1 , comprising a dispersion medium.
10. The composition containing an inorganic solid electrolyte according to claim 9, wherein The dispersion medium is selected from ketone compounds, aliphatic compounds and ester compounds. 11 . A sheet for an all-solid-state secondary battery, comprising a layer composed of the composition containing an inorganic solid electrolyte according to claim 1 . 12 . An electrode sheet for an all-solid-state secondary battery, comprising an active material layer, wherein the active material layer is composed of the composition containing an inorganic solid electrolyte according to claim 1 .
13. An all-solid-state secondary battery, comprising, in sequence, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein: At least one of the positive electrode active material layer and the negative electrode active material layer is a layer composed of the composition containing an inorganic solid electrolyte according to any one of claims 1 to 10. 14 . A method for producing a sheet for an all-solid-state secondary battery, comprising forming a film of the composition containing an inorganic solid electrolyte according to claim 1 . 15 . A method for manufacturing an all-solid-state secondary battery, comprising manufacturing the all-solid-state secondary battery by the manufacturing method according to claim 14 .
Citation Information
Patent Citations
Latex agglutination reaction measuring instrument
JP1987022066A
Catalyst carrier and production thereof
JP1990006856A
Four-wheel steering device
JP1991045473A
Distortion compensator
JP1993090844A
Assignment decision support system
JP1994004516A